Environmental assessment of carbon mitigation retrofit pathways in integrated BF-BOF steel plants under electricity supply scenarios - S. Pascual; C. Barón; M. Bailera; B. Peña; E. Llera; P. Lisbona (Sustainable Production and Consumption, 2026)

Hotter days, smaller ranges: Air temperature constrains livestock movement and space use in Mediterranean rangelands - Lara Naves-Alegre; Roberto Pascual-Rico; José Antonio Sánchez-Zapata; Antonio Contreras; Marina Rincón-Madroñero; Jose Manuel Zamora-Marín; Jomar M. Barbosa (Journal of Environmental Management, 2026)

Exposure conditions control plastic degradation in marine environments: Evidence from UV, floating, and intertidal experiments - Esteban Pascual-Parra; Ainhoa Hernández-García; Javier Pérez-Barbería; Andrés Arias; José M. Rico (Environmental Pollution, 2026)

Electrochemically generated metal-doped 2D-cobalt(M)MOFs@C derivatives for boosting the electrocatalytic oxidation of glycerol to formate - Sergio Hernández-Salvador; Jose Luis del Río-Rodríguez; Miguel A. Montiel; M. Asunción Molina; Silvia Gutiérrez-Tarriño; Juan José Calvente; Andrew M. Beale; Pascual Oña-Burgos; José Solla-Gullón; José Luis Olloqui-Sariego (Chemical Engineering Journal, 2026)

Corporations and financial institutions driving coastal conflicts involving Indigenous Peoples - Sebastian Villasante; Julia Tovar Verba; Veronica Relano; Sílvia Gómez; José Bakit; Nathan J. Bennett; Anthony Charles; Rafael Calderón-Contreras; Andrés M. Cisneros-Montemayor; Bernardo M. Flores; Lucas A. Garibaldi; Maria Grazia Pennino; et al. (Ambio, 2026)
Socio-environmental conflicts associated with large-scale economic projects in Indigenous territories are well documented, but conflicts in coastal areas remain largely unexplored, despite the crucial differences between inland and coastal ecosystems. While the empirical literature about socio-environmental conflicts in Indigenous territories in coastal areas is growing, the role of financial institutions and corporations in these conflicts is often overlooked. This study addresses this gap by examining the financial institutions and corporations associated with more than 400 reported socio-environmental conflicts affecting Indigenous Peoples in coastal areas worldwide. Our results show that most financial institutions supporting projects linked to conflicts are based in West Europe and North America, with North American financial institutions linked to multiple projects. The energy sector accounts for the highest number of socio-environmental conflicts, particularly those involving corporations operating across continents. Many European and North American corporations operate mostly in Africa, but also globally. Corporations with overseas operations are associated with a higher intensity of conflicts. These findings highlight the need to scrutinize financial investments and corporate practices driving socio-environmental conflicts in coastal Indigenous territories, where human rights are often at risk. The lack of due diligence and accountability in applying environmental and social safeguards weakens protections for both ecosystems and Indigenous communities. Strengthening the enforcement of national and international laws on environmental sustainability, human rights and Indigenous rights is therefore essential for coastal development projects.

3D tool for monitoring fouling in small vessels from Asturias, Bay of Biscay - I. Carrera-Rodríguez; V. Soto-López; Ricardo López-Alonso; Esteban Pascual-Parra; Claudia González-Toral; Andrés Arias; Eduardo Cires; J.A. García-Maza; M. Bartolomé; D. Menéndez-Teleña (Journal of Marine Systems, 2026)

Revalorization of brewer’s spent grain through solid-state fermentation with Pleurotus ostreatus - Mariano M. Pascual; Julio C. Painefilú; Natalia Ranalli; M. Victoria Santos; Mariana E. Langenheim; Marilina Campos; Valeria Jurski; Carlos M. Luquet (Food and Humanity, 2026)

Challenges and recommendations for marine waste management in European fishing ports - Cristina Pita; Gillian B. Ainsworth; Marina Astudillo-Pascual; Priscila M. Silva; Angel Gutierrez; Sebastian Villasante (Frontiers in Marine Science, 2026)
The fishing sector plays a crucial role in the effective management of marine litter, emphasising the importance of facilitating waste collection for fishers and ensuring its subsequent management in port reception facilities (PRFs). EU Directive 2019/883/EU provides a unified sector-specific legal framework for managing ship-generated waste within EU ports, but harmonising PRFs and waste management remains challenging across Member States. Key areas for improving waste management include streamlining the regulatory framework (policies and processes), enhancing economic viability, fostering partnerships, promoting knowledge sharing, improving infrastructure, and increasing stakeholder awareness. The measures taken should consider the context, including port characteristics and the country in which it operates.

Modeling and evaluating longitudinal brain maintenance and cognitive reserve using episodic memory, brain structure, and functional connectivity in older adults - Rachel M. Morse; Lídia Vaqué-Alcázar; María Cabello-Toscano; Cristina Solé-Padullés; Lídia Mulet-Pons; Juan Pablo Martin Trias; Micael Andersson; Dídac Vidal-Piñeiro; Alvaro Pascual-Leone; Kristine Walhovd; Lars Nyberg; David Bartres-Faz (GeroScience, 2026)
Cognitive reserve (CR) and brain maintenance (BM) reflect better than expected cognition despite brain pathology and minimal age-related brain changes that explain stable cognition, respectively. Despite being commonly used, joint quantification of these concepts has been limited; our aim is to derive longitudinal CR and BM measures and investigate CR’s relationship with education and functional connectivity. We analyzed longitudinal data from 451 participants (241 female, age mean = 68.5 years, follow-up mean = 4.2 years). From a hippocampus change-memory change regression, we modeled BM as memory stability relative to hippocampal stability and CR as better-than-expected memory stability relative to hippocampal atrophy. We examined whether education and resting-state functional connectivity (Default Mode, Executive Control and anterior Salience Network) (1) moderated the hippocampal-memory relationship using linear mixed effects models (LMEs), (2) moderated the hippocampus change-memory change relationship using linear regressions, and (3) were associated with our CR measure using LMEs. Analyses adjusted for demographics and MRI scanner/cohort, using false discovery rate (FDR) for multiple comparisons. From a significant hippocampus change-memory change relationship ( β = 0.130, p FDR = 0.016, r 2 = 0.282), we derived continuous CR and BM measures, providing subject-level estimates. Salience Network connectivity moderated the hippocampal-memory relationship ( β = − 0.070, p FDR = 0.046, marginal r 2 = 0.179). No variable moderated the hippocampus change-memory change relationship or correlated with our CR measure, consistent with the measure’s longitudinal definition. Our CR and BM measures refine phenotyping of aging trajectories. CR may be expressed through increased Salience Network connectivity, preserving memory level in the presence of hippocampal atrophy. Future work should delineate longitudinal CR mechanisms that decouple memory change from hippocampal atrophy.

Photocontrol of nitrogen sites for poisoning-free NO₂ sensing - Berta Pérez-Román; Daniel Matatagui; M. Alejandra Mazo; Pilar Marín; Laura Pascual; Jesús López-Sánchez; Fernando Rubio-Marcos (Chemical Engineering Journal, 2026)

A consortium of arbuscular mycorrhizal fungi and plant growth-promoting bacteria modulates wine grape ripening and composition under climate change conditions - Daria Kozikova; Johann Martínez-Lüscher; M. Carmen Antolín; Nieves Goicoechea; Inmaculada Pascual (Food Research International, 2026)

1H-NMR metabolomics reveals that astaxanthin nanoemulsion reverses liver damage by promoting restoration of energy and lipid metabolism - S. Bautista-Hernández; L. A. Pascual-Pineda; S. Herrera-Meza; R. García-Román; M. Jiménez-Fernández; R. V. García-Rodríguez; A. Sánchez-Medina (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Functional characterization of splice variants in hereditary breast and ovarian cancer susceptibility genes - Laura Rosado-Jiménez; Younes Mestre-Terkemani; Ángeles García-Aliaga; María D. Sarabia-Meseguer; Miguel Marín-Vera; José A. Macías-Cerrolaza; Pilar Sánchez-Henarejos; María R. García-Hernández; Marta Zafra-Poves; Beatriz C. Álvarez-Abril; Carmen B. López-Sánchez; María P. Moya-Martínez; et al. (Familial Cancer, 2025)

Machine learning-based assessment of sustainable extraction methodologies tackling the biotechnological exploitation of Arnica montana extracts - Paula Garcia-Oliveira; Lucía Cassani; Aurora Silva; Clara Grosso; M. Fátima Barroso; Miguel A. Prieto; Jesus Simal-Gandara; Luigi Lucini; Pascual García-Pérez (Food Chemistry, 2025)

Role of α and δ’ phases in the piezoelectric response of in situ poled electrospun ferroelectric polyamide 11 fibers - A. Leonés; C. Pascual-González; H. Amorín; J.P. Fernández-Blázquez; M. Algueró; M.E.G. Mosquera; V. Sessini (Chemical Engineering Journal, 2025)

The effect of sustainable management practices on the bacterial community in different European croplands - J. Cuartero; B. Frey; R. Zornoza; V. Sánchez-Navarro; L. Canfora; O. Özbolat; M. Egea-Cortines; R. Farina; H. Fritze; T. Tuomivirta; K. Lång; R. Lemola; et al. (Applied Soil Ecology, 2025)

An Upper Devonian foredeep basin in the Southern Central Iberian Zone (Variscan Iberian Massif): Consequences for Variscan plate dynamics - Francisco J. Rubio Pascual; Luis M. Martín Parra; Jerónimo Matas; L. Roberto Rodríguez Fernández; Luis González Menéndez; Diana Moreno-Martín; Rubén Díez Fernández (Tectonophysics, 2025)

Improving small urban wastewater treatment plants with a nature-based reactor for tertiary treatment - Lluís Bertrans-Tubau; Sergio Martínez-Campos; Julio C. López-Doval; Meritxell Abril; Guillem Pladelasala-Rocafiguera; Sergio Ponsá; Ana Cristina Suñer; Victoria Salvadó; Manuela Hidalgo; Anna Doménech-Pascual; Anna M. Romaní; Anna Pico-Tomàs; et al. (Journal of Environmental Management, 2025)

Molecular architecture strategies for UV-enhanced NO2 sensors under ambient conditions - Berta Pérez-Román; Jesús López-Sánchez; M. Alejandra Mazo; Álvaro Peña; David G. Calatayud; Pilar Marín; Laura Pascual; Rocío E. Rojas-Hernández; Daniel Matatagui; Fernando Rubio-Marcos (Chemical Engineering Journal, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

P19-34 Ontogeny of Drug-Induced Steatosis: From Key Initiating Events to Disease Phenotypes - E. López-Pascual; M. Moreno-Torres; E. Moro; P. Soluyanova; A. Rapisarda; R. Ortega-Vallbona; E. Serrano-Candelas; R. Gozalbes; R. Jover; J.V. Castell (Toxicology Letters, 2025)

P19-31 Unraveling drug-induced hepatic steatosis: clinical sub-phenotypes, prognosis prediction and identification of high-concern drugs and hazardous chemical attributes - M. Moreno-Torres; E. López-Pascual; E. Moro; A. Rapisarda; B. Lindeman; A. Verhoeven; T. Luechtefeld; E. Serrano-Candelas; H. Dirven; J.V. Castell; R. Jover (Toxicology Letters, 2025)

Effect of Lacticaseibacillus rhamnosus on carotenoid stability and metabolomic profile during red pepper paste fermentation - K.P. Barrientos-López; S. Bautista-Hernández; M.P. Jiménez-Escobar; M. Jiménez-Fernández; M.P. Rascón-Díaz; A. Sánchez-Medina; C.I. Beristain; L.A. Pascual-Pineda (Food Bioscience, 2025)

Soil functions are shaped by aridity through soil properties and the microbial community structure - Anna Doménech-Pascual; Luciana Chavez Rodriguez; Xingguo Han; Joan Pere Casas-Ruiz; Joan Ferriol-Ciurana; Jonathan Donhauser; Karen Jordaan; Steven D. Allison; Aline Frossard; Anders Priemé; Jean-Baptiste Ramond; Anna M. Romaní (Applied Soil Ecology, 2025)

Expression landscape of epigenetic genes in human hepatocellular carcinoma - Borja Castelló-Uribe; Amaya López-Pascual; Jasmin Elurbide; Elena Adán-Villaescusa; Emiliana Valbuena-Goiricelaya; Luz A. Martinez-Perez; Iker Uriarte; M. Ujúe Latasa; Bruno Sangro; María Arechederra; Carmen Berasain; Matías A. Avila; et al. (Journal of Physiology and Biochemistry, 2025)
Hepatocellular carcinoma (HCC) is the most common primary liver tumor, often arising in the context of chronic liver disease. Despite recent advances in systemic therapies, including the use of immune checkpoint inhibitors (ICIs), clinical outcomes remain suboptimal, with many patients exhibiting primary or acquired resistance. Accumulating evidence indicates that the dysregulation of epigenetic mechanisms contributes to HCC development, and may also play a crucial role in shaping the tumor immune microenvironment, influencing responses to treatments. In this study, we analyzed the expression profiles of a comprehensive set of epigenetic regulators across publicly available transcriptomic datasets of HCC and non-tumoral liver tissues. Our findings reveal a consistent dysregulation of key epigenetic modifiers, particularly those involved in DNA methylation and histone modification. Furthermore, our analysis underscores the need for a deeper understanding of the epigenetic landscape of HCC, as specific epigenetic patterns are directly associated with disease development, the major mutational, immune, and transcriptional subclasses of HCC, and patient clinical outcomes. Our study provides a foundation for integrating epigenetic biomarkers into patient stratification and therapeutic decision-making. A more comprehensive analysis of epigenetic alterations could pave the way for novel predictive markers and combination strategies that could enhance the efficacy of ICIs in HCC.

Microbial colonization and function of biofilms developing on plastics and bioplastics in a pristine mountain stream ecosystem - Mar Oliva‐Albert; Alba Bellostas‐Carreras; José Luis Guijosa‐Ortega; Anna Doménech‐Pascual; Judit Boadella; Joan Pere Casas‐Ruiz; David Pineda‐Morante; Yoann Menard; Laura Ayuso; Anna Lupon; Eugènia Martí; Helena Guasch; et al. (Limnology and Oceanography, 2025)
Streams naturally receive allochthonous particulate organic materials, but human activity may contribute additional plastic litter inputs, which can affect ecosystem functioning. Our objective was to assess the effect of plastic and bioplastic inputs on microbial biomass and function in a pristine mountain stream. To do that, fragments of plastics (polyethylene—PE, polypropylene—PP), bioplastics (polyhydroxyalkanoate—PHA, polylactic acid—PLA), and wood (as a natural material) were immersed in the stream and collected after 120, 202, 316, and 383 d. Fungal, prokaryotic, and algal biomass, and autotrophic and heterotrophic functions (net primary production, extracellular enzyme activities, and nutrient uptake) were analyzed together with organic matter weight changes over time. Wood showed high fungal and prokaryotic biomass, phosphatase and β‐glucosidase activities, and a significant weight loss, as related to the degradation process. In contrast, plastics and bioplastics did not lose weight and were mainly colonized by algae, suggesting that they serve as an inert surface and over‐enhance primary production. However, phenol oxidase (ligninolytic enzyme) activity in plastics and bioplastics was similar to that in wood and increased with time together with heterotrophic biomass. This indicates that plastispheres can contribute to the degradation of plastics and bioplastics, which may become a carbon source in the long term. Overall, the observed dynamics of microbial biomass and metabolism in the plastispheres point to their potential effect on stream nutrient and carbon cycles. The study highlights the need for careful human activities in pristine mountain watersheds to avoid altering their ecosystem functioning.

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

Nutritional improvement of wheat grains and soybeans by solid-state fermentation with Pleurotus ostreatus mycelium - Mariano M. Pascual; Lucila T. Herbert; Marilina Campos; Valeria Jurski; Julio C. Painefilú; Carlos M. Luquet (Innovative Food Science & Emerging Technologies, 2025)

Fosfomycin in bacteraemic urinary tract infection due to multidrug-resistant Escherichia coli : insights of post hoc DOOR analysis of the FOREST trial - Jesús Sojo-Dorado; Inmaculada López-Hernández; Belén Gutiérrez-Gutiérrez; Sandra De la Rosa-Riestra; Fernando Docobo-Pérez; Alicia Hernánez-Torres; Álvaro Pascual; Jesús Rodriguez-Baño; Esperanza Merino de Lucas; Laura Escolà-Vergé; Elena Bereciartua; Elisa García-Vázquez; et al. (Infectious Diseases, 2025)

Key conservation actions for European steppes in the context of the Post-2020 Global Biodiversity Framework - Cristian Pérez-Granados; Ana Benítez-López; Mario Díaz; João Gameiro; Bernd Lenzner; Núria Roura-Pascual; Julia Gómez-Catasús; Rocío Tarjuelo; Adrián Barrero; Luis Bolonio; Gerard Bota; Mattia Brambilla; et al. (Sustainability Science, 2025)
The Kunming–Montreal Global Biodiversity Framework (KM–GBF) envisions a world living in harmony with nature by 2050, with 23 intermediate targets to be achieved by 2030. However, aligning international policy and national and local implementation of effective actions can be challenging. Using steppe birds, one of the most threatened vertebrate groups in Europe, as a model system, we identified 36 conservation actions for the achievement of the KM–GBF targets and we singled out—through an expert-based consensus approach—ten priority actions for immediate implementation. Three of these priority actions address at least five of the first eight KM–GBF targets, those related to the direct causes of biodiversity loss, and collectively cover all the targets when implemented concurrently. These actions include (i) effectively protecting priority areas, (ii) implementing on-the-ground habitat management actions, and (iii) improving the quality and integration of monitoring programmes. Our findings provide a blueprint for implementing effective strategies to halt biodiversity loss in steppe-like ecosystems. Our approach can be adapted to other taxonomic groups and ecosystems and has the potential to serve as a catalyst for policy-makers, prompting a transition from political commitment to tangible actions, thereby facilitating the attainment of the KM–GBF targets by 2030.

Anthropogenic pressures driving the salinity intrusion in the Guadalquivir estuary: insights from 1D numerical simulations - Sara Sirviente; Juan J. Gomiz-Pascual; Marina Bolado-Penagos; Sabine Sauvage; José M. Sánchez-Pérez; Miguel Bruno (Ocean Science, 2025)
The study presents a dynamic analysis of the present-day behavior of salinity concentration in the Guadalquivir estuary and evaluates the impact of anthropogenic pressures on the dynamics of the horizontal salinity gradient. A one-dimensional (1D) hydrodynamic model with an advection and dispersion module is used to study the effects of human pressure involved in the salinity concentration along the estuary. The observations, which correspond to continuous measurements taken during different oceanographic campaigns from 2021 to 2023, show an excessive salt intrusion in the estuary (with salinities of 5 psu at 60 km from the mouth) compared to the idealized situation when anthropogenic water withdrawals are absent. This highlights the need to include a water withdrawal term in the simulations to accurately reproduce the system's real behavior, thereby reflecting the magnitude of anthropogenic pressures. The model successfully reproduces the observations when this forcing factor is included. Under constant low-flow conditions, experiments show that increasing water withdrawals leads to an increase in the horizontal salinity gradient upstream. Similarly, under constant water withdrawal conditions, a decrease in the horizontal salinity gradient is observed when freshwater flows exceed 40 m3 s−1. Variations in anthropogenic pressures, such as water withdrawals for agriculture or the saline industry and reductions in freshwater flow, play a fundamental role in the evolution of salinity along the estuary. Under the current circumstances, the Guadalquivir estuary requires an urgent regulation of these uses in order to avoid further damage to the aquatic ecosystems.

Calibration of GEDI footprint aboveground biomass models in Mediterranean forests with NFI plots: A comparison of approaches - Adrián Pascual; Paul B. May; Aarón Cárdenas-Martínez; Juan Guerra-Hernández; Neha Hunka; Jamis M. Bruening; Sean P. Healey; John D. Armston; Ralph O. Dubayah (Journal of Environmental Management, 2025)

Flexible and multifunctional P(VDF-TrFE)/BT-BMT polymer composite films: Realizing high piezoelectric performance and electrocaloric effect - Indrani Coondoo; Vahideh B. Isfahani; Harvey Amorín; Igor Bdikin; João Carvalho; Cristina Pascual-González; Bruna M. Silva; João Oliveira; D. Pukazhselvan; Bernardo G. Almeida; Georgina Miranda (Chemical Engineering Journal, 2025)

Publisher Correction: Business-as-usual trends will largely miss 2030 global conservation targets - Ignacio Palomo; Alberto González-García; Paul J. Ferraro; Roldan Muradian; Unai Pascual; Manuel Arboledas; James M. Bullock; Enora Bruley; Erik Gómez-Baggethun; Sandra Lavorel (Ambio, 2025)

Business-as-usual trends will largely miss 2030 global conservation targets - Ignacio Palomo; Alberto González-García; Paul J. Ferraro; Roldan Muradian; Unai Pascual; Manuel Arboledas; James M. Bullock; Enora Bruley; Erik Gómez-Baggethun; Sandra Lavorel (Ambio, 2025)
To address climate change and global biodiversity loss, the world must hit three important international conservation targets by 2030: protect 30% of terrestrial and marine areas, halt and reverse forest loss, and restore 350 Mha of degraded and deforested landscapes. Here, we (1) provide estimates of the gaps between these globally agreed targets and business-as-usual trends; (2) identify examples of rapid past trend-shifts towards achieving the targets; and (3) link these past trend-shifts to different levers. Our results suggest that under a business-as-usual scenario, the world will fail to achieve all three targets. However, trend-shifts that rapidly “bend the curve” have happened in the past and these should therefore be fostered. These trend-shifts are linked to transformative change levers that include environmental governance, economic factors, values, and knowledge. Further research on trend-shifts, as well as bold action on underlying levers, is urgently needed to meet 2030 global conservation targets.

Geographic and Biological Drivers Shape Anthropogenic Extinctions in the Macaronesian Vascular Flora - Raúl Orihuela‐Rivero; Javier Morente‐López; J. Alfredo Reyes‐Betancort; Hanno Schaefer; Alfredo Valido; Miguel Menezes de Sequeira; Maria M. Romeiras; Carlos A. Góis‐Marques; Marcos Salas‐Pascual; Alain Vanderpoorten; José María Fernández‐Palacios; Jairo Patiño (Global Change Biology, 2025)
Whether species extinctions have accelerated during the Anthropocene and the extent to which certain species are more susceptible to extinction due to their ecological preferences and intrinsic biological traits are among the most pressing questions in conservation biology. Assessing extinction rates is, however, challenging, as best exemplified by the phenomenon of ‘ dark extinctions ’: the loss of species that disappear before they are even formally described. These issues are particularly problematic in oceanic islands, where species exhibit high rates of endemism and unique biological traits but are also among the most vulnerable to extinction. Here, we document plant species extinctions since Linnaeus' Species Plantarum in Macaronesia, a biogeographic region comprised of five hyperdiverse oceanic archipelagos, and identify the key drivers behind these extinctions. We compiled 168 records covering 126 taxa, identifying 13 global and 155 local extinction events. Significantly higher extinction rates were observed compared to the expected global background rate. We uncovered differentiated extinction patterns along altitudinal gradients, highlighting a recent coastal hotspot linked to socioeconomic changes in Macaronesian archipelagos from the 1960s onwards. Key factors influencing extinction patterns include island age, elevation, introduced herbivorous mammals, and human population size. Trait‐based analyses across the floras of the Azores and Canary Islands revealed that endemicity, pollination by vertebrates, nitrogen‐fixing capacity, woodiness, and zoochory consistently tended to increase extinction risk. Our findings emphasize the critical role of geography and biological traits, alongside anthropogenic impacts, in shaping extinction dynamics on oceanic islands. Enhancing our knowledge of life‐history traits within island floras is crucial for accurately predicting and mitigating future extinction risks, underscoring the urgent need for comprehensive biodiversity assessments in island ecosystems.

Management Measures and Trends of Biological Invasions in Europe: A Survey‐Based Assessment of Local Managers - Carla Garcia‐Lozano; Josep Pueyo‐Ros; Quim Canelles; Guillaume Latombe; Tim Adriaens; Sven Bacher; Ana Cristina Cardoso; Michelle Cleary; Lluís Coromina; Franck Courchamp; Wayne Dawson; Maarten de Groot; et al. (Global Change Biology, 2025)
Biological invasions are a major threat to biodiversity, ecosystem functioning and nature's contributions to people worldwide. However, the effectiveness of invasive alien species (IAS) management measures and the progress toward achieving biodiversity targets remain uncertain due to limited and nonuniform data availability. Management success is usually assessed at a local level and documented in technical reports, often written in languages other than English, which makes such data notoriously difficult to collect at large geographic scales. Here we present the first European assessment of how managers perceive trends in IAS and the effectiveness of management measures to mitigate biological invasions. We developed a structured questionnaire translated into 18 languages and disseminated it to local and regional managers of IAS in Europe. We received responses from 1928 participants from 41 European countries, including 24 European Union (EU) Member States. Our results reveal substantial efforts in IAS monitoring and control, with invasive plants being the primary focus. Yet, there is a general perception of an increase in the numbers, occupied areas, and impacts of IAS across environment and taxonomic groups, particularly plants, over time. This perceived increase is consistent across both EU and non‐EU countries, with respondents from EU countries demonstrating more certainty in their responses. Our results also indicate a lack of data on alien vertebrates and invertebrates, reflecting a need for more targeted monitoring and knowledge sharing between managers and policymakers and between countries. Overall, our study suggests that Europe's current strategies are insufficient to substantially reduce IAS by 2030 and hence to meet the Kunming‐Montreal Global Biodiversity Framework target.

Eco-efficiency assessment of carbon capture and hydrogen transition as decarbonisation strategies in alumina production - Javier Sáez-Guinoa; Inés Senante; Sara Pascual; Eva Llera-Sastresa; Luis M. Romeo (Journal of Cleaner Production, 2024)

Urinary concentrations of non-essential and essential elements during weaning in infants from the NELA cohort in Spain - Leyre Notario-Barandiaran; Eva Morales; Jesús Vioque; Carmen Martinez-Gracia; Marina Santaella-Pascual; Clara Suarez-Martinez; Luis Garcia-Marcos; Margaret R. Karagas; Antonio J. Signes-Pastor; M.E. Candel-Torralba; L. Garcia-Marcos (Pi); M.J. Gimenez-Banon; et al. (Environmental Research, 2024)

Buffer properties in the Guadalquivir Estuary (SW Iberian Peninsula) - J. Sánchez-Rodríguez; S. Sirviente; A. Sierra; J.J. Gómiz-Pascual; M. Bolado-Penagos; M. Bruno; J. Forja; T. Ortega (Estuarine, Coastal and Shelf Science, 2024)

A sarcoptic mange outbreak drives long-term patterns of a fitness trait in an exotic ungulate - Roberto Pascual-Rico; José A. Sánchez-Zapata; Mónica G. Candela; Sergio Eguía; Jomar M. Barbosa (European Journal of Wildlife Research, 2024)
Species phenotypes are driven by persistent selective pressures that condition their adaptation to the environment. However, stochastic critical events, such as disease outbreaks, may also act as selective pressures because of drastic population decline. External structures like horns of ungulate species may reflect the consequences of these selective pressures on animal fitness. Using a generalized linear model approach, we analysed how a massive mortality event caused by a sarcoptic mange outbreak in 1992 affected the horn size of an Iberian aoudad population (dataset from 1980 to 2014) by comparing horn length before and after the outbreak. We found that this episodic, albeit massive, outbreak changed long-term trends in age-size horn relations. Both females and males presented shorter horns after the sarcoptic mange outbreak, although more marked in males. Even when animals reached mature ages, horn length did not increase with age to the same degree as before the outbreak. We consider that two processes may have acted on the population: a bottleneck favoured “shorter horns” phenotype and a post-mange enzootic period limited horn growth, as infected animals may invest more resources in the immune system. Overall, our results show a top-down regulation of a fitness trait for an ungulate population mediated by a parasite. This disease outbreak showed long-lasting effects on the ungulate population, with ecological and management implications. Graphical Abstract

Upgrading and validating a soil water balance model to predict stem water potential in vineyards - José M. Mirás-Avalos; José M. Escalona; Eva Pilar Pérez-Álvarez; Pascual Romero; Pablo Botia; Josefa Navarro; Nazareth Torres; Luis Gonzaga Santesteban; David Uriarte; Diego S. Intrigliolo; I. Buesa (Agricultural and Forest Meteorology, 2024)

Assessing impacts of observations on ocean circulation models with examples from coastal, shelf, and marginal seas - Christopher A. Edwards; Pierre De Mey-Frémaux; Bàrbara Barceló-Llull; Guillaume Charria; Byoung-Ju Choi; George R. Halliwell; Lars R. Hole; Colette Kerry; Vassiliki H. Kourafalou; Alexander L. Kurapov; Andrew M. Moore; Baptiste Mourre; et al. (Frontiers in Marine Science, 2024)
Ocean observing systems in coastal, shelf and marginal seas collect diverse oceanographic information supporting a wide range of socioeconomic needs, but observations are necessarily sparse in space and/or time due to practical limitations. Ocean analysis and forecast systems capitalize on such observations, producing data-constrained, four-dimensional oceanographic fields. Here we review efforts to quantify the impact of ocean observations, observing platforms, and networks of platforms on model products of the physical ocean state in coastal regions. Quantitative assessment must consider a variety of issues including observation operators that sample models, error of representativeness, and correlated uncertainty in observations. Observing System Experiments, Observing System Simulation Experiments, representer functions and array modes, observation impacts, and algorithms based on artificial intelligence all offer methods to evaluate data-based model performance improvements according to metrics that characterize oceanographic features of local interest. Applications from globally distributed coastal ocean modeling systems document broad adoption of quantitative methods, generally meaningful reductions in model-data discrepancies from observation assimilation, and support for assimilation of complementary data sets, including subsurface in situ observation platforms, across diverse coastal environments.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Grapevine varieties show different sensitivities to flavonoid alterations caused by high temperatures under two irrigation conditions - Inmaculada Pascual; Johann Martínez-Lüscher; Juan José Irigoyen; Nieves Goicoechea; M. Carmen Antolín (Food Research International, 2024)

Reviewing the science on 50 years of conservation: Knowledge production biases and lessons for practice - Neil M. Dawson; Brendan Coolsaet; Aditi Bhardwaj; David Brown; Bosco Lliso; Jacqueline Loos; Laura Mannocci; Adrian Martin; Malena Oliva; Unai Pascual; Pasang Sherpa; Thomas Worsdell (Ambio, 2024)
Drawing on 662 studies from 102 countries, we present a systematic review of published empirical studies about site-level biodiversity conservation initiated between 1970 and 2019. Within this sample, we find that knowledge production about the Global South is largely produced by researchers in the Global North, implying a neocolonial power dynamic. We also find evidence of bias in reported ecological outcomes linked to lack of independence in scientific studies, serving to uphold narratives about who should lead conservation. We explore relationships in the sample studies between conservation initiative types, the extent of Indigenous Peoples’ and local communities’ influence in governance, and reported social and ecological outcomes. Findings reveal positive ecological and social outcomes are strongly associated with higher levels of influence of Indigenous Peoples and local communities and their institutions, implying equity in conservation practice should be advanced not only for moral reasons, but because it can enhance conservation effectiveness.

Leafiness-LiDAR index and NDVI for identification of temporal patterns in super-intensive almond orchards as response to different management strategies - L. Sandonís-Pozo; B. Oger; B. Tisseyre; J. Llorens; A. Escolà; M. Pascual; J.A. Martínez-Casasnovas (European Journal of Agronomy, 2024)

“Hg distribution and accumulation in soil and vegetation in areas impacted by artisanal gold mining in the Southern Amazonian region of Madre de Dios, Peru.” - Maria J. Rodriguez-Pascual; Claudia M. Vega; Natasha Andrade; Luis E. Fernández; Miles R. Silman; Alba Torrents (Chemosphere, 2024)

Lead exerts a depression of neurotransmitter release through a blockade of voltage dependent calcium channels in chromaffin cells - Victoria Jiménez Carretero; Ninfa Liccardi; Maria Arribas Tejedor; Ricardo de Pascual; Jorge Hernández Campano; Jesús M. Hernández-Guijo (Toxicology, 2024)

Differential response of bacteria and fungi to drought on the decomposition of Sarcocornia fruticosa woody stems in a saline stream - Anna Doménech‐Pascual; Lorena Carrasco‐Barea; Frederic Gich; Judit Boadella; Zeus Freixinos Campillo; Rosa Gómez Cerezo; Andrea Butturini; Anna M. Romaní (Environmental Microbiology, 2024)
Inland saline ecosystems suffer multiple stresses (e.g., high radiation, salinity, water scarcity) that may compromise essential ecosystem functions such as organic matter decomposition. Here, we investigated the effects of drought on microbial colonization and decomposition of Sarcocornia fruticosa woody stems across different habitats in a saline watershed: on the dry floodplain, submerged in the stream channel and at the shoreline (first submerged, then emerged). Unexpectedly, weight loss was not enhanced in the submerged stems, while decomposition process differed between habitats. On the floodplain, it was dominated by fungi and high cellulolytic activity; in submerged conditions, a diverse community of bacteria and high ligninolytic activity dominated; and, on the shoreline, enzyme activities were like submerged conditions, but with a fungal community similar to the dry conditions. Results indicate distinct degradation paths being driven by different stress factors: strong water scarcity and photodegradation in dry conditions, and high salinity and reduced oxygen in wet conditions. This suggests that fungi are more resistant to drought, and bacteria to salinity. Overall, in saline watersheds, variations in multiple stress factors exert distinct environmental filters on bacteria and fungi and their role in the decomposition of plant material, affecting carbon cycling and microbial interactions.

Predicting plant–pollinator interactions: concepts, methods, and challenges - Guadalupe Peralta; Paul J. CaraDonna; Demetra Rakosy; Jochen Fründ; María P. Pascual Tudanca; Carsten F. Dormann; Laura A. Burkle; Christopher N. Kaiser-Bunbury; Tiffany M. Knight; Julian Resasco; Rachael Winfree; Nico Blüthgen; et al. (Trends in Ecology & Evolution, 2024)

Corrigendum to “Optimization of electrocoagulation process for treatment of rice mill effluent using response surface methodology” [J. Water Process Eng., volume 49 (October 2022) 103074] - A. Ronaldo Anuf; K. Ramaraj; Vishnu Sankar Sivasankarapillai; Ragupathy Dhanusuraman; J. Prakash Maran; G. Rajeshkumar; Abbas Rahdar; Ana M. Díez-Pascual (Journal of Water Process Engineering, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Hydroxyapatite modified poly(acrylic acid)/polyethylene glycol sustainable drug delivery nanocomposite prepared via double emulsion with bitter almond oil - Ali Aslani; Mehrab Pourmadadi; Majid Abdouss; Abbas Rahdar; Ana M. Díez-Pascual (Sustainable Chemistry and Pharmacy, 2024)

Stenotic nasopharyngeal dysgenesis and suspect muscular dystrophy in a Jack Russell Terrier - S. Degl'innocenti; W. West; M. Pascual Moreno; A. Ortiz (Journal of Comparative Pathology, 2024)

A new vertebrate assemblage from the Matute Formation of the Cameros Basin (Ágreda, Spain): implications for the diversity during the Jurassic/Cretaceous boundary - E. Puértolas-Pascual; M. Aurell; D. D. Bermúdez-Rochas; J. I. Canudo; A. E. Fernandes; A. Galobart; M. Moreno-Azanza; A. Pérez-García; D. Castanera (Journal of Iberian Geology, 2024)
The Ribota site (Ágreda, Soria, Spain) is a new locality in the Matute Formation (Tithonian–Berriasian) composed of several carbonate layers, outstandingly rich in macrovertebrate remains. Fossils show an unusual replacement of the original bioapatite by quartz, and are found as positive reliefs protruding from lacustrine limestone beds. This type of conservation has allowed the identification of around one hundred vertebrate bone accumulations in an outcrop of more than 10 hectares. Osteichthyans (articulated partial skeletons, cranial material, and isolated postcranial bones and scales), crocodylomorphs (disarticulated cranial material, isolated teeth, vertebrae and osteoderms), turtles (partial carapaces and plastra, but also isolated plates) and pterosaurs (cranial and appendicular elements) have been identified. Around 80 specimens have been collected and a preliminary study of part of the collection (35 specimens) has allowed the identification of at least 5 different taxa: Halecomorphi indet., Neoginglymodi indet., Goniopholididae indet., Testudinata indet., and Pterodactyloidea indet. This new site represents one of the few sites from this time interval preserved in a fully lacustrine environment, so these vertebrate assemblages are unique and composed of different animals that presumably lived around and within the lake. They are dominated by aquatic and amphibian vertebrates and was formed by attrition in this lacustrine environment, possibly far from the lake shoreline. These macrovertebrate assemblages provide new data about the diversity in the faunal ecosystems from the Jurassic/Cretaceous transition of the Iberian Basin Rift System.

Activity of imipenem/relebactam and comparators against KPC-producing Klebsiella pneumoniae and imipenem-resistant Pseudomonas aeruginosa - Mercedes Delgado-Valverde; Inés Portillo-Calderón; Manuel Alcalde-Rico; M. Carmen Conejo; Carmen Hidalgo; Carlos del Toro Esperón; Álvaro Pascual (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose Relebactam is a novel β-lactamase inhibitor, which, when combined with imipenem/cilastatin, is active against both class A and class C β-lactamases. To evaluate in vitro antimicrobial activity of imipenem/relebactam against a collection of recent clinical isolates of carbapenem-non-susceptible P. aeruginosa and K. pneumoniae ST258 and ST512 KPC producers belonging to different lineages from hospitals in Southern Spain. Methods Six hundred and seventy-eight isolates were tested: 265 K. pneumoniae (230 ST512/KPC-3 and 35 ST258/KPC-3) and 413 carbapenem-non-susceptible P. aeruginosa . Imipenem, piperacillin/tazobactam, ceftazidime, cefepime, aztreonam, ceftolozane/tazobactam, meropenem, amikacin, ciprofloxacin, colistin, and ceftazidime/avibactam were used as comparators against P. aeruginosa . Against K. pneumoniae ceftazidime, cefepime, aztreonam, and ceftolozane/tazobactam were not tested, and tigecycline was studied instead. MICs were determined in duplicate by broth microdilution according to EUCAST guidelines. Results Imipenem/relebactam displayed potent in vitro activity against both sequence types of KPC-3-producing K. pneumoniae . MIC 50 and MIC 90 values were 0.25 mg/L and 1 mg/L, respectively, with percent of susceptible isolates >97%. Only three K. pneumoniae ST512/KPC-3 isolates and one ST258/KPC-3 were resistant to imipenem/relebactam. Relebactam sensitized 98.5% of K. pneumoniae isolates resistant to imipenem. The activity of imipenem/relebactam against P. aeruginosa was moderate (susceptibility rate: 62.7%). Analysis of the acquired and mutational resistome of isolates with high levels of resistance to imipenem/relebactam has not shown a clear association between them. Conclusion Imipenem/relebactam showed excellent activity against K. pneumoniae KPC-3. The activity of imipenem/relebactam against imipenem-resistant P. aeruginosa was moderate.

Two new coastal time-series of seawater carbonate system variables in the NW Mediterranean Sea: rates and mechanisms controlling pH changes - Maribel I. García-Ibáñez; Elisa F. Guallart; Arturo Lucas; Josep Pascual; Josep M. Gasol; Cèlia Marrasé; Eva Calvo; Carles Pelejero (Frontiers in Marine Science, 2024)
In this work, we present, for the first time, the seawater carbonate system measurements of two coastal time-series in the NW Mediterranean Sea, L’Estartit Oceanographic Station (EOS; 42.05°N 3.2542°E) and the Blanes Bay Microbial Observatory (BBMO; 41.665°N 2.805°E). At these two time-series, measurements of total alkalinity (TA), pH, and associated variables, such as dissolved inorganic nutrients, temperature, and salinity, have been performed monthly since 2010 in surface seawater. Seasonality and seasonal amplitude are analogous in both time-series, with seasonality in pH T in situ (pH at in situ seawater conditions on the total hydrogen ion scale) primarily determined by seasonality in sea surface temperature. The evaluated pH T in situ trends at BBMO (-0.0021 ± 0.0003 yr -1 ) and EOS (-0.0028 ± 0.0005 yr -1 ) agree with those reported for coastal and open ocean surface waters in the Mediterranean Sea and open ocean surface waters of the global ocean, therefore indicating that these time-series are representative of global ocean acidification signals despite being coastal. The decreases in pH T in situ can be attributed to increases in total dissolved inorganic carbon (DIC; 1.5 ± 0.4 µmol kg -1 yr -1 at BBMO and 1.6 ± 0.6 µmolESkg -1 yr -1 at EOS) and sea surface temperature (0.08 ± 0.02 °C yr -1 at BBMO and 0.08 ± 0.04 °C yr -1 at EOS). The increases in carbon dioxide fugacity ( f CO 2 ; 2.4 ± 0.3 µmol kg -1 yr -1 at BBMO and 2.9 ± 0.6 µmol kg -1 yr -1 at EOS) follow the atmospheric CO 2 forcing, thus indicating the observed DIC increase is related to anthropogenic CO 2 uptake. The increasing trends in TA (1.2 ± 0.3 µmol kg -1 yr -1 at BBMO and 1.0 ± 0.5 µmol kg -1 yr -1 at EOS) buffered the acidification rates, counteracting 60% and 72% of the pH T in situ decrease caused by increasing DIC at EOS and BBMO, respectively. Once accounted for the neutralizing effect of TA increase, the rapid sea surface warming plays a larger role in the observed pH decreases (43% at EOS and 62% at BBMO) than the DIC increase (36% at EOS and 33% at BBMO).

Tectonics and geothermal gradients from subduction to collision in the NW Variscan Iberian Massif - Francisco J. Rubio Pascual; Luis M. Martín Parra; Rubén Díez Fernández; Pablo Valverde-Vaquero; Alejandro Díez-Montes; Manuel P. Hacar Rodríguez; Justo Iglesias; Gloria Gallastegui; L. Roberto Rodríguez Fernández; Aratz Beranoaguirre (International Geology Review, 2024)

Horizontal flow aerated constructed wetlands for municipal wastewater treatment: The influence of bed depth - A. Pascual; J.A. Álvarez; D. de la Varga; C.A. Arias; D. Van Oirschot; R. Kilian; M. Soto (Science of The Total Environment, 2024)

Mediterranean springs: Keystone ecosystems and biodiversity refugia threatened by global change - M. Fernández‐Martínez; J. Barquín; N. Bonada; M. Cantonati; C. Churro; J. Corbera; C. Delgado; M. Dulsat‐Masvidal; G. Garcia; O. Margalef; R. Pascual; J. Peñuelas; et al. (Global Change Biology, 2024)
Mediterranean spring ecosystems are unique habitats at the interface between surface water and groundwater. These ecosystems support a remarkable array of biodiversity and provide important ecological functions and ecosystem services. Spring ecosystems are influenced by abiotic, biotic, and anthropogenic factors such as the lithology of their draining aquifers, their climate, and the land use of their recharge area, all of which affect the water chemistry of the aquifer and the spring discharges. One of the most relevant characteristics of spring ecosystems is the temporal stability of environmental conditions, including physicochemical features of the spring water, across seasons and years. This stability allows a wide range of species to benefit from these ecosystems (particularly during dry periods), fostering an unusually high number of endemic species. However, global change poses important threats to these freshwater ecosystems. Changes in temperature, evapotranspiration, and precipitation patterns can alter the water balance and chemistry of spring water. Eutrophication due to agricultural practices and emergent pollutants, such as pharmaceuticals, personal care products, and pesticides, is also a growing concern for the preservation of spring biodiversity. Here, we provide a synthesis of the main characteristics and functioning of Mediterranean spring ecosystems. We then describe their ecological value and biodiversity patterns and highlight the main risks these ecosystems face. Moreover, we identify existing knowledge gaps to guide future research in order to fully uncover the hidden biodiversity within these habitats and understand the main drivers that govern them. Finally, we provide a brief summary of recommended actions that should be taken to effectively manage and preserve Mediterranean spring ecosystems for future generations. Even though studies on Mediterranean spring ecosystems are still scarce, our review shows there are sufficient data to conclude that their future viability as functional ecosystems is under severe threat.

Taxonomic status of deep-sea sharks Deania calceus and D. hystricosa (Centrophoridae) - M. Marrero; P.J. Pascual-Alayón; M.V. Martin; I. Casañas; M. Freitas; M. Hernández (Regional Studies in Marine Science, 2023)

Dynamics of Atmospheric-Driven Surface Currents on The Gulf of Cadiz Continental Shelf and its link with The Strait of Gibraltar and The Western Alboran Sea - S. Sirviente; M. Bolado-Penagos; J.J. Gomiz-Pascual; J. Romero-Cózar; A. Vázquez; M Bruno (Progress in Oceanography, 2023)

Microencapsulation of betalains by foam fluidized drying - A. Morales-Huerta; E. Flores-Andrade; M. Jiménez-Fernández; C.I. Beristain; L.A. Pascual-Pineda (Journal of Food Engineering, 2023)

Bottom up anatase monodisperse nanoparticles grown on sepiolite showing high thermal stability and optimal optical properties for self-cleaning applications - M.F. Acosta; M. Morales; G. Marcelo; S. López-Esteban; A. Esteban-Cubillo; P.M. Rodríguez-Pascual; C. Pecharromán (Applied Clay Science, 2023)

Habitat‐based biodiversity responses to macroclimate and edaphic factors in European fen ecosystems - Borja Jiménez‐Alfaro; Liene Aunina; Michele Carbognani; Daniel Dítě; Eduardo Fernández‐Pascual; Emmanuel Garbolino; Ondřej Hájek; Petra Hájková; Tatiana G. Ivchenko; Ute Jandt; Florian Jansen; Tiina H. M. Kolari; et al. (Global Change Biology, 2023)
Understanding large‐scale drivers of biodiversity in palustrine wetlands is challenging due to the combined effects of macroclimate and local edaphic conditions. In boreal and temperate fen ecosystems, the influence of macroclimate on biodiversity is modulated by hydrological settings across habitats, making it difficult to assess their vulnerability to climate change. Here, we investigate the influence of macroclimate and edaphic factors on three Essential Biodiversity Variables across eight ecologically defined habitats that align with ecosystem classifications and red lists. We used 27,555 vegetation plot samples from European fens to assess the influence of macroclimate and groundwater pH predictors on the geographic distribution of each habitat type. Additionally, we modeled the relative influence of macroclimate, water pH, and water table depth on community species richness and composition, focusing on 309 plant specialists. Our models reveal strong effects of mean annual temperature, diurnal thermal range, and summer temperature on biodiversity variables, with contrasting differences among habitats. While macroclimatic factors primarily shape geographic distributions and species richness, edaphic factors emerge as the primary drivers of composition for vascular plants and bryophytes. Annual precipitation exhibits non‐linear effects on fen biodiversity, with varying impact across habitats with different hydrological characteristics, suggesting a minimum requirement of 600 mm of annual precipitation for the occurrence of fen ecosystems. Our results anticipate potential impacts of climate warming on European fens, with predictable changes among habitat types and geographic regions. Moreover, we provide evidence that the drivers of biodiversity in boreal and temperate fens are closely tied to the ecological characteristics of each habitat type and the dispersal abilities of bryophytes and vascular plants. Given that the influence of macroclimate and edaphic factors on fen ecosystems is habitat specific, climate change research and conservation actions should consider ecological differentiation within functional IUCN ecosystems at continental and regional scales.

Comprehensive analysis of epigenetic and epitranscriptomic genes’ expression in human NAFLD - Jose M. Herranz; Amaya López-Pascual; Alex Clavería-Cabello; Iker Uriarte; M. Ujúe Latasa; Ainara Irigaray-Miramon; Elena Adán-Villaescusa; Borja Castelló-Uribe; Bruno Sangro; María Arechederra; Carmen Berasain; Matías A. Avila; et al. (Journal of Physiology and Biochemistry, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a multifactorial condition with a complex etiology. Its incidence is increasing globally in parallel with the obesity epidemic, and it is now considered the most common liver disease in Western countries. The precise mechanisms underlying the development and progression of NAFLD are complex and still poorly understood. The dysregulation of epigenetic and epitranscriptomic mechanisms is increasingly recognized to play pathogenic roles in multiple conditions, including chronic liver diseases. Here, we have performed a comprehensive analysis of the expression of epigenetic and epitranscriptomic genes in a total of 903 liver tissue samples corresponding to patients with normal liver, obese patients, and patients with non-alcoholic fatty liver (NAFL) and non-alcoholic steatohepatitis (NASH), advancing stages in NAFLD progression. We integrated ten transcriptomic datasets in an unbiased manner, enabling their robust analysis and comparison. We describe the complete landscape of epigenetic and epitranscriptomic genes’ expression along the course of the disease. We identify signatures of genes significantly dysregulated in association with disease progression, particularly with liver fibrosis development. Most of these epigenetic and epitranscriptomic effectors have not been previously described in human NAFLD, and their altered expression may have pathogenic implications. We also performed a comprehensive analysis of the expression of enzymes involved in the metabolism of the substrates and cofactors of epigenetic and epitranscriptomic effectors. This study provides novel information on NAFLD pathogenesis and may also guide the identification of drug targets to treat this condition and its progression towards hepatocellular carcinoma.

Food nanostructuring of paprika capsules obtained by coacervation for improving carotenoid storage stability - E. Flores-Andrade; M. Jiménez-Fernández; C.I. Beristain; E. Azuara; G.F. Gutiérrez-López; L. Alamilla-Beltrán; L.A. Pascual-Pineda (Food Structure, 2023)

An inclusive typology of values for navigating transformations towards a just and sustainable future - Christopher M. Raymond; Christopher B. Anderson; Simone Athayde; Arild Vatn; Ariane M. Amin; Paola Arias-Arévalo; Michael Christie; Mariana Cantú-Fernández; Rachelle K. Gould; Austin Himes; Jasper O. Kenter; Dominic Lenzi; et al. (Current Opinion in Environmental Sustainability, 2023)

OS02-01: Novel clinical phenotypes and chemical classifications in drug-induced cholestasis: analysis of a database of 390 patients developed by collaborative literature review and machine learning support - M. Moreno Torres; E. Lopez Pascual; A.S. Rapisarda; G. López; T. Bozada Jr; J. Jiang; J. van Ertvelde; I.-L. Steffensen; B. Lindeman; T. Luechtefeld; H. Dirven; M. Vinken; et al. (Toxicology Letters, 2023)

DUACS DT2021 reprocessed altimetry improves sea level retrieval in the coastal band of the European seas - Antonio Sánchez-Román; M. Isabelle Pujol; Yannice Faugère; Ananda Pascual (Ocean Science, 2023)
More than 29 years of altimeter data have been recently reprocessed by the multi-satellite Data Unification and Altimeter Combination System (DUACS) and made available under the name of DT2021 through the Copernicus Marine Service (CMEMS) and the Copernicus Climate Change Service (C3S). New standards have been applied and various geophysical correction parameters have been updated compared to the previous release in order to improve the product quality. This paper describes the assessment of this new release through the comparison of both the all satellites and the two satellites product with external in situ tide gauge measurements in the coastal areas of the European seas for a time period from 1 January 1993 to 31 May 2020. The aim is to quantify the improvements on the previous DT2018 processing version for the retrieval of sea level in the coastal zone. The results confirmed that the CMEMS product in the new DT2021 processing version better solves the signal in the coastal band. The all satellites dataset showed a reduction of 3 % in errors when compared with tide gauges and of 5 % in the variance of the differences between the datasets compared to DT2018 reprocessing. Moreover, the all satellites dataset provided more accurate sea level measurements when making a comparison with tide gauges with respect to the climatic two satellites dataset due to the better performance of the former for the assessment of higher than climatic frequency signals. By contrast, the two satellite dataset is the most suitable product for the assessment of long-term sea level sea surface height (SSH) trends in the coastal zone due to its larger stability to the detriment of the all satellites dataset.

Assessing the performance of NASA’s GEDI L4A footprint aboveground biomass density models using National Forest Inventory and airborne laser scanning data in Mediterranean forest ecosystems - Adrián Pascual; Juan Guerra-Hernández; John Armston; David M. Minor; Laura I. Duncanson; Paul B. May; James R. Kellner; Ralph Dubayah (Forest Ecology and Management, 2023)

Solar-driven calcium looping in fluidized beds for thermochemical energy storage - Claudio Tregambi; Francesca Di Lauro; Sara Pascual; Pilar Lisbona; Luis M. Romeo; Roberto Solimene; Piero Salatino; Fabio Montagnaro (Chemical Engineering Journal, 2023)

Connected Conservation: Rethinking conservation for a telecoupled world - Rachel Carmenta; Jos Barlow; Mairon G. Bastos Lima; Erika Berenguer; Shofwan Choiruzzad; Natalia Estrada-Carmona; Filipe França; Giorgos Kallis; Evan Killick; Alexander Lees; Adrian Martin; Unai Pascual; et al. (Biological Conservation, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

Tidal dynamics on the upper continental slope of the eastern Gulf of Cádiz: The interplay between water masses and its effects on seafloor morphology - D. Roque; J.J. Gomiz-Pascual; M. Bruno; R. Sánchez-Leal; C.J. González; M. García; L.M. Fernández-Salas; F.J. Hernández-Molina (Progress in Oceanography, 2023)

Capacity of countries to reduce biological invasions - Guillaume Latombe; Hanno Seebens; Bernd Lenzner; Franck Courchamp; Stefan Dullinger; Marina Golivets; Ingolf Kühn; Brian Leung; Núria Roura-Pascual; Emma Cebrian; Wayne Dawson; Christophe Diagne; et al. (Sustainability Science, 2023)
The extent and impacts of biological invasions on biodiversity are largely shaped by an array of socio-economic and environmental factors, which exhibit high variation among countries. Yet, a global analysis of how these factors vary across countries is currently lacking. Here, we investigate how five broad, country-specific socio-economic and environmental indices (Governance, Trade, Environmental Performance, Lifestyle and Education, Innovation) explain country-level (1) established alien species (EAS) richness of eight taxonomic groups, and (2) proactive or reactive capacity to prevent and manage biological invasions and their impacts. These indices underpin many aspects of the invasion process, including the introduction, establishment, spread and management of alien species. They are also general enough to enable a global comparison across countries, and are therefore essential for defining future scenarios for biological invasions. Models including Trade, Governance, Lifestyle and Education, or a combination of these, best explained EAS richness across taxonomic groups and national proactive or reactive capacity. Historical (1996 or averaged over 1996–2015) levels of Governance and Trade better explained both EAS richness and the capacity of countries to manage invasions than more recent (2015) levels, revealing a historical legacy with important implications for the future of biological invasions. Using Governance and Trade to define a two-dimensional socio-economic space in which the position of a country captures its capacity to address issues of biological invasions, we identified four main clusters of countries in 2015. Most countries had an increase in Trade over the past 25 years, but trajectories were more geographically heterogeneous for Governance. Declines in levels of Governance are concerning as they may be responsible for larger levels of invasions in the future. By identifying the factors influencing EAS richness and the regions most susceptible to changes in these factors, our results provide novel insights to integrate biological invasions into scenarios of biodiversity change to better inform decision-making for policy and the management of biological invasions.

Determination of soluble angiotensin-converting enzyme 2 in saliva samples and its association with nicotine - Samuel Bru; Adrián González-Marrón; Cristina Lidón-Moyano; Reyes Carballar; Joan Marc Martínez-Láinez; Hipólito Pérez-Martín; Marcela Fu; Raúl Pérez-Ortuño; Montse Ballbè; Jose A. Pascual; Esteve Fernández; Josep Clotet; et al. (Environmental Research, 2023)

Satellite multispectral indices to estimate canopy parameters and within-field management zones in super-intensive almond orchards - L. Sandonís-Pozo; J. Llorens; A. Escolà; J. Arnó; M. Pascual; J. A. Martínez-Casasnovas (Precision Agriculture, 2022)
Continuous canopy status monitoring is an essential factor to support and precisely apply orchard management actions such as pruning, pesticide and foliar treatment applications, or fertirrigation, among others. For that, this work proposes the use of multispectral vegetation indices to estimate geometric and structural orchard parameters from remote sensing images (high temporal and spatial resolution) as an alternative to more time-consuming processing techniques, such as LiDAR surveys or UAV photogrammetry. A super-intensive almond ( Prunus dulcis ) orchard was scanned using a mobile terrestrial laser (LiDAR) in two different vegetative stages (after spring pruning and before harvesting). From the LiDAR point cloud, canopy orchard parameters, including maximum height and width, cross-sectional area and porosity, were summarized every 0.5 m along the rows and interpolated using block kriging to the pixel centroids of PlanetScope (3 × 3 m) and Sentinel-2 (10 × 10 m) image grids. To study the association between the LiDAR-derived parameters and 4 different vegetation indices. A canonical correlation analysis was carried out, showing the normalized difference vegetation index (NDVI) and the green normalized difference vegetation index (GNDVI) to have the best correlations. A cluster analysis was also performed. Results can be considered optimistic both for PlanetScope and Sentinel-2 images to delimit within-field management zones, being supported by significant differences in LiDAR-derived canopy parameters.

Assessment of potential selection bias in neuroimaging studies of postoperative delirium and cognitive decline: lessons from the SAGES study - Michele Cavallari; Tamara G. Fong; Alexandra Touroutoglou; Bradford C. Dickerson; Eva Schmitt; Thomas G. Travison; Edward R. Marcantonio; Long H. Ngo; Towia Libermann; Alvaro Pascual-Leone; Mouhsin M. Shafi; Sharon K. Inouye; et al. (Brain Imaging and Behavior, 2022)

Biological invasions reveal how niche change affects the transferability of species distribution models - Chunlong Liu; Christian Wolter; Franck Courchamp; Núria Roura‐Pascual; Jonathan M. Jeschke (Ecology, 2022)
Species distribution models (SDMs) have been widely applied to predict geographic ranges of species across space and time under the assumption of niche conservatism (i.e., species niches change very slowly). However, an increasing number of studies have reported evidence of rapid niche changes across space and time, which has sparked a widespread debate on whether SDMs can be transferred to new areas or time periods. Understanding how niche changes affect SDM transferability is thus crucial for the future application and improvement of SDMs. Biological invasions provide an opportunity to address this question due to the geographically independent distributions and diverse patterns of niche changes between species’ native and introduced ranges. Here, we synthesized findings on 217 species from 50 studies to elucidate the effects of niche change on the spatial transferability of SDMs. When niche change was considered as a categorical classification (conserved vs. shifted niches) in tests of the niche conservatism hypothesis, SDM transferability was markedly lower for species with a shifted niche in their introduced range. When niche change was measured as numerical dynamics between native and introduced niches, SDM transferability was high for species occupying similar environmental conditions in both ranges and low for species with more environmental space remaining unoccupied in the introduced range. Surprisingly, the number of presence points used for developing SDMs turned out to have an even stronger effect on transferability. Our results thus reveal detrimental effects of both niche change and lack of presence points on SDM transferability. It is necessary to consider both niche change and data quality for improving the transferability of SDMs, so that they can better support conservation management and policy decisions.

Methodological approach to spatial analysis of agricultural pest dispersal in olive landscapes - A. Moreno; A. J. Rescia; S. Pascual; M. Ortega (Environmental Monitoring and Assessment, 2022)
The effectiveness of a Geographical Information Systems cost-distance tool for detecting landscape permeability in relation to the movement of pests in olive landscapes was established. The simplification of agricultural systems is linked to an increased incidence of pests on crops. Therefore, it is important to understand the impact of different land uses surrounding olive groves on pests. In this work, we analysed the effect of the structure of the olive landscape on the movement of two main olive pests—the olive fruit fly, Bactrocera oleae (Rossi) (Diptera: Tephritidae) and the olive moth, Prays oleae (Bernard) (Lepidopetera: Praydidae). We applied linear mixed effects models to analyse the relationship between pest abundance and cost-distance, using different hypotheses to evaluate those land uses that are favourable or unfavourable for the movement of these pests. The results show that this methodology is effective in detecting possible unfavourable land uses with a barrier effect, such as woodland and artificial land uses, and favourable land uses with a corridor effect such as olive groves. Whether other land uses, such as scrubland or riverbanks, act as a barrier or corridor depends on the pest and its life cycle stage. The effect that different land uses have in maintaining low levels of pest populations and ensuring the long-term sustainability of these agricultural systems are discussed. The implications of landscape permeability for the physical structure of the landscape and the dispersal of organisms, and the potential of that landscape to impact the continuous flow of natural processes are also addressed.

Global DNA methylation and cellular 5-methylcytosine and H4 acetylated patterns in primary and secondary dormant seeds of Capsella bursa-pastoris (L.) Medik. (shepherd’s purse) - Sara Gomez-Cabellos; Peter E. Toorop; María Jesús Cañal; Pietro P. M. Iannetta; Eduardo Fernández-Pascual; Hugh W. Pritchard; Anne M. Visscher (Protoplasma, 2022)
Despite the importance of dormancy and dormancy cycling for plants’ fitness and life cycle phenology, a comprehensive characterization of the global and cellular epigenetic patterns across space and time in different seed dormancy states is lacking. Using Capsella bursa-pastoris (L.) Medik. (shepherd’s purse) seeds with primary and secondary dormancy, we investigated the dynamics of global genomic DNA methylation and explored the spatio-temporal distribution of 5-methylcytosine (5-mC) and histone H4 acetylated (H4Ac) epigenetic marks. Seeds were imbibed at 30 °C in a light regime to maintain primary dormancy, or in darkness to induce secondary dormancy. An ELISA-based method was used to quantify DNA methylation, in relation to total genomic cytosines. Immunolocalization of 5-mC and H4Ac within whole seeds (i.e., including testa) was assessed with reference to embryo anatomy. Global DNA methylation levels were highest in prolonged (14 days) imbibed primary dormant seeds, with more 5-mC marked nuclei present only in specific parts of the seed (e.g., SAM and cotyledons). In secondary dormant seeds, global methylation levels and 5-mC signal where higher at 3 and 7 days than 1 or 14 days. With respect to acetylation, seeds had fewer H4Ac marked nuclei (e.g., SAM) in deeper dormant states, for both types of dormancy. However, the RAM still showed signal after 14 days of imbibition under dormancy-inducing conditions, suggesting a central role for the radicle/RAM in the response to perceived ambient changes and the adjustment of the seed dormancy state. Thus, we show that seed dormancy involves extensive cellular remodeling of DNA methylation and H4 acetylation.

The value of transhumance for biodiversity conservation: Vulture foraging in relation to livestock movements - Natividad Aguilera-Alcalá; Eneko Arrondo; Roberto Pascual-Rico; Zebensui Morales-Reyes; José M. Gil-Sánchez; José A. Donázar; Marcos Moleón; José A. Sánchez-Zapata (Ambio, 2022)
In recent decades, intensive techniques of livestock raising have flourished, which has largely replaced traditional farming practices such as transhumance. These changes may have affected scavengers’ behaviour and ecology, as extensive livestock is a key source of carrion. This study evaluates the spatial responses of avian scavengers to the seasonal movements of transhumant herds in south-eastern Spain. We surveyed the abundance of avian scavengers and ungulates, and analysed the factors affecting the space use by 30 GPS-tracked griffon vultures ( Gyps fulvus ). Griffons’ foraging activity increased in the pasturelands occupied by transhumant herds, which implied greater vulture abundance at the landscape level during the livestock season. In contrast, facultative scavengers were more abundant without transhumant livestock herds, and the abundance of wild ungulates did not change in relation to livestock presence. We conclude that fostering transhumance and other traditional farming systems, to the detriment of farming intensification, could favour vulture conservation.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Phase-Amplitude Coupling and Phase Synchronization Between Medial Temporal, Frontal and Posterior Brain Regions Support Episodic Autobiographical Memory Recall - Nicolas Roehri; Lucie Bréchet; Martin Seeber; Alvaro Pascual-Leone; Christoph M. Michel (Brain Topography, 2022)
Episodic autobiographical memory (EAM) is a complex cognitive function that emerges from the coordination of specific and distant brain regions. Specific brain rhythms, namely theta and gamma oscillations and their synchronization, are thought of as putative mechanisms enabling EAM. Yet, the mechanisms of inter-regional interaction in the EAM network remain unclear in humans at the whole brain level. To investigate this, we analyzed EEG recordings of participants instructed to retrieve autobiographical episodes. EEG recordings were projected in the source space, and time-courses of atlas-based brain regions-of-interest (ROIs) were derived. Directed phase synchrony in high theta (7–10 Hz) and gamma (30–80 Hz) bands and high theta-gamma phase-amplitude coupling were computed between each pair of ROIs. Using network-based statistics, a graph-theory method, we found statistically significant networks for each investigated mechanism. In the gamma band, two sub-networks were found, one between the posterior cingulate cortex (PCC) and the medial temporal lobe (MTL) and another within the medial frontal areas. In the high theta band, we found a PCC to ventromedial prefrontal cortex (vmPFC) network. In phase-amplitude coupling, we found the high theta phase of the left MTL biasing the gamma amplitude of posterior regions and the vmPFC. Other regions of the temporal lobe and the insula were also phase biasing the vmPFC. These findings suggest that EAM, rather than emerging from a single mechanism at a single frequency, involves precise spatio-temporal signatures mapping on distinct memory processes. We propose that the MTL orchestrates activity in vmPFC and PCC via precise phase-amplitude coupling, with vmPFC and PCC interaction via high theta phase synchrony and gamma synchronization contributing to bind information within the PCC-MTL sub-network or valuate the candidate memory within the medial frontal sub-network.

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System - Adèle Révelard; Joaquín Tintoré; Jacques Verron; Pierre Bahurel; John A. Barth; Mathieu Belbéoch; Jérôme Benveniste; Pascal Bonnefond; Eric P. Chassignet; Sophie Cravatte; Fraser Davidson; Brad deYoung; et al. (Frontiers in Marine Science, 2022)
Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean observing value chain, from the design and deployment of multi-platform observations to their analysis and the delivery of products, sometimes through data assimilation in numerical models. Despite significant advances over the last two decades in more cooperation across the ocean observing activities, this integrated approach has not yet been fully realized. The ocean observing system still suffers from organizational silos due to independent and often disconnected initiatives, the strong and sometimes destructive competition across disciplines and among scientists, and the absence of a well-established overall governance framework. Here, we address the need for enhanced organizational integration among all the actors of ocean observing, focusing on the occidental systems. We advocate for a major evolution in the way we collaborate, calling for transformative scientific, cultural, behavioral, and management changes. This is timely because we now have the scientific and technical capabilities as well as urgent societal and political drivers. The ambition of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) and the various efforts to grow a sustainable ocean economy and effective ocean protection efforts all require a more integrated approach to ocean observing. After analyzing the barriers that currently prevent this full integration within the occidental systems, we suggest nine approaches for breaking down the silos and promoting better coordination and sharing. These recommendations are related to the organizational framework, the ocean science culture, the system of recognition and rewards, the data management system, the ocean governance structure, and the ocean observing drivers and funding. These reflections are intended to provide food for thought for further dialogue between all parties involved and trigger concrete actions to foster a real transformational change in ocean observing.

In vitro and in silico studies for barbinervic acid, a triterpene isolated from Eugenia punicifolia that inhibits vasopressor tone - Rafaela G. S. Teixeira; Ricardo de Pascual; Kátia G. Lima-Araújo; Monique A. de Brito; Cristobal de los Rios; Artur F. do Carmo; Luis Gandía; Cláudia L. M. Silva; Thelma B. Machado; Wilson C. Santos (Natural Product Research, 2021)

Structural connectivity and subcellular changes after antidepressant doses of ketamine and Ro 25-6981 in the rat: an MRI and immuno-labeling study - Raquel Pascual-Antón; Arantxa Blasco-Serra; Emma Muñoz-Moreno; Fuencisla Pilar-Cuéllar; Emilio Garro-Martínez; Eva Florensa-Zanuy; Xavier López-Gil; Víctor M. Campa; Guadalupe Soria; Albert Adell (Brain Structure and Function, 2021)
Ketamine has rapid and robust antidepressant effects. However, unwanted psychotomimetic effects limit its widespread use. Hence, several studies examined whether GluN2B-subunit selective NMDA antagonists would exhibit a better therapeutic profile. Although preclinical work has revealed some of the mechanisms of action of ketamine at cellular and molecular levels, the impact on brain circuitry is poorly understood. Several neuroimaging studies have examined the functional changes in the brain induced by acute administration of ketamine and Ro 25-6981 (a GluN2B-subunit selective antagonist), but the changes in the microstructure of gray and white matter have received less attention. Here, the effects of ketamine and Ro 25-6981 on gray and white matter integrity in male Sprague–Dawley rats were determined using diffusion-weighted magnetic resonance imaging (DWI). In addition, DWI-based structural brain networks were estimated and connectivity metrics were computed at the regional level. Immunohistochemical analyses were also performed to determine whether changes in myelin basic protein (MBP) and neurofilament heavy-chain protein (NF200) may underlie connectivity changes. In general, ketamine and Ro 25-6981 showed some opposite structural alterations, but both compounds coincided only in increasing the fractional anisotropy in infralimbic prefrontal cortex and dorsal raphe nucleus. These changes were associated with increments of NF200 in deep layers of the infralimbic cortex (together with increased MBP) and the dorsal raphe nucleus. Our results suggest that the synthesis of NF200 and MBP may contribute to the formation of new dendritic spines and myelination, respectively. We also suggest that the increase of fractional anisotropy of the infralimbic and dorsal raphe nucleus areas could represent a biomarker of a rapid antidepressant response.

First Assessment of the Impacts of the COVID-19 Pandemic on Global Marine Recreational Fisheries - Pablo Pita; Gillian B. Ainsworth; Bernardino Alba; Antônio B. Anderson; Manel Antelo; Josep Alós; Iñaki Artetxe; Jérôme Baudrier; José J. Castro; Belén Chicharro; Karim Erzini; Keno Ferter; et al. (Frontiers in Marine Science, 2021)
This work is the result of an international research effort to determine the main impacts of the COVID-19 pandemic on marine recreational fishing. Changes were assessed on (1) access to fishing, derived from lockdowns and other mobility restrictions; (2) ecosystems, because of alterations in fishing intensity and human presence; (3) the blue economy, derived from alterations in the investments and expenses of the fishers; and (4) society, in relation to variations in fishers’ health and well-being. For this, a consultation with experts from 16 countries was carried out, as well as an international online survey aimed at recreational fishers, that included specific questions designed to capture fishers’ heterogeneity in relation to behavior, skills and know-how, and vital involvement. Fishers’ participation in the online survey (5,998 recreational fishers in 15 countries) was promoted through a marketing campaign. The sensitivity of the fishers’ clustering procedure, based on the captured heterogeneity, was evaluated by SIMPER analysis and by generalized linear models. Results from the expert consultation highlighted a worldwide reduction in marine recreational fishing activity. Lower human-driven pressures are expected to generate some benefits for marine ecosystems. However, experts also identified high negative impacts on the blue economy, as well as on fisher health and well-being because of the loss of recreational fishing opportunities. Most (98%) of the fishers who participated in the online survey were identified as advanced , showing a much higher degree of commitment to recreational fishing than basic fishers (2%). Advanced fishers were, in general, more pessimistic about the impacts of COVID-19, reporting higher reductions in physical activity and fish consumption, as well as poorer quality of night rest, foul mood, and raised more concerns about their health status. Controlled and safe access to marine recreational fisheries during pandemics would provide benefits to the health and well-being of people and reduce negative socioeconomic impacts, especially for vulnerable social groups.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Alternative futures for global biological invasions - Núria Roura-Pascual; Brian Leung; Wolfgang Rabitsch; Lucas Rutting; Joost Vervoort; Sven Bacher; Stefan Dullinger; Karl-Heinz Erb; Jonathan M. Jeschke; Stelios Katsanevakis; Ingolf Kühn; Bernd Lenzner; et al. (Sustainability Science, 2021)
Scenario analysis has emerged as a key tool to analyze complex and uncertain future socio-ecological developments. However, currently existing global scenarios (narratives of how the world may develop) have neglected biological invasions, a major threat to biodiversity and the economy. Here, we use a novel participatory process to develop a diverse set of global biological invasion scenarios spanning a wide range of plausible global futures through to 2050. We adapted the widely used “two axes” scenario analysis approach to develop four families of four scenarios each, resulting in 16 scenarios that were later clustered into four contrasting sets of futures. Our analysis highlights that socioeconomic developments and technological innovation have the potential to shape biological invasions, in addition to well-known drivers, such as climate and human land use change and global trade. Our scenarios partially align with the shared socioeconomic pathways created by the climate change research community. Several factors that drive differences in biological invasions were underrepresented in the shared socioeconomic pathways; in particular, the implementation of biosecurity policies. We argue that including factors related to public environmental awareness and technological and trade development in global scenarios and models is essential to adequately consider biological invasions in global environmental assessments and thereby obtain a more integrative picture of future social–ecological developments.

Fermented dairy foods rich in probiotics and cardiometabolic risk factors: a narrative review from prospective cohort studies - Judit Companys; Anna Pedret; Rosa M Valls; Rosa Solà; Vicente Pascual (Critical Reviews in Food Science and Nutrition, 2021)

Long-Term Changes in the Water Mass Properties in the Balearic Channels Over the Period 1996–2019 - Manuel Vargas-Yáñez; Mélanie Juza; M. Carmen García-Martínez; Francina Moya; Rosa Balbín; Enrique Ballesteros; María Muñoz; Elena Tel; Josep Pascual; Pedro Vélez-Belchí; Jordi Salat (Frontiers in Marine Science, 2021)
The analysis of a 24-year time series of Conductivity-Temperature-Depth (CTD) casts collected in the Balearic Channels (1996–2019) has allowed detecting and quantifying long-term changes in water mass properties in the Western Mediterranean. For the complete period, the intermediate waters have experienced warming and salting at rates of 1.4°C/100yr and 0.3–0.6/100yr for the Western Intermediate Water, and 1°C/100yr and 0.3–0.4/100yr for the Levantine Intermediate Water. The density of these two water masses has not changed. The deep waters, defined as those denser than 29.1 kg/m 3 , showed positive trends in temperature, salinity, and density (0.8°C/100yr, 0.2/100yr, and 0.02 kg.m –3 /100yr, respectively). The high temporal variability of the upper layer makes the detection of long-term changes more difficult. Nevertheless, combining CTD data with temperature data from the oceanographic station at L’Estartit and simulated data from the NCEP/NCAR reanalysis, it can be established that the Atlantic Water increased its temperature at a rate of 2.1–2.8°C/100yr and likely its salinity at a rate of 0.6/100yr. The water column absorbed heat at a rate equivalent to 1–1.2 W/m 2 . All these trends are much higher than those reported in previous works (more than double in some cases). The warming of the water column produced an increase in the thermosteric component of sea level. However, this increase was compensated by the decrease in the halosteric component. Besides these changes, other alterations related to the Western Mediterranean Transition have been observed over shorter periods. The temperature and salinity of the intermediate waters increased before the winter of 2004/2005 and then the temperature and salinity of the deep waters increased dramatically in 2005. The density of the deep water reached values unprecedented before 2005. Deep and intermediate waters were uplifted by the presence of such dense deep waters. The arrival of warmer and saltier intermediate waters from the Eastern Mediterranean is also observed, mainly after 2010.

Correction to: Framing natural assets for advancing sustainability research: translating different perspectives into actions - Maria Jose Martinez-Harms; Stefan Gelcich; Rainer M. Krug; Fleur J. F. Maseyk; Hannah Moersberger; Archi Rastogi; Geoffrey Wambugu; Cornelia B. Krug; Eva M. Spehn; Unai Pascual (Sustainability Science, 2021)
In the original publication of the article, under the acknowledgments section, the project number was published incorrectly.

Drivers of future alien species impacts: An expert‐based assessment - Franz Essl; Bernd Lenzner; Sven Bacher; Sarah Bailey; Cesar Capinha; Curtis Daehler; Stefan Dullinger; Piero Genovesi; Cang Hui; Philip E. Hulme; Jonathan M. Jeschke; Stelios Katsanevakis; et al. (Global Change Biology, 2020)
Understanding the likely future impacts of biological invasions is crucial yet highly challenging given the multiple relevant environmental, socio‐economic and societal contexts and drivers. In the absence of quantitative models, methods based on expert knowledge are the best option for assessing future invasion trajectories. Here, we present an expert assessment of the drivers of potential alien species impacts under contrasting scenarios and socioecological contexts through the mid‐21st century. Based on responses from 36 experts in biological invasions, moderate (20%–30%) increases in invasions, compared to the current conditions, are expected to cause major impacts on biodiversity in most socioecological contexts. Three main drivers of biological invasions—transport, climate change and socio‐economic change—were predicted to significantly affect future impacts of alien species on biodiversity even under a best‐case scenario. Other drivers (e.g. human demography and migration in tropical and subtropical regions) were also of high importance in specific global contexts (e.g. for individual taxonomic groups or biomes). We show that some best‐case scenarios can substantially reduce potential future impacts of biological invasions. However, rapid and comprehensive actions are necessary to use this potential and achieve the goals of the Post‐2020 Framework of the Convention on Biological Diversity.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Looks can be deceiving: Didemnum pseudovexillum sp. nov. (Ascidiacea) in European harbours - X. Turon; M. Casso; M. Pascual; F. Viard (Marine Biodiversity, 2020)

EEG Functional Connectivity is a Weak Predictor of Causal Brain Interactions - Jord J. T. Vink; Deborah C. W. Klooster; Recep A. Ozdemir; M. Brandon Westover; Alvaro Pascual-Leone; Mouhsin M. Shafi (Brain Topography, 2020)

Effects of deficit irrigation on the yield and irrigation water use efficiency of drip-irrigated sweet pepper (Capsicum annuum L.) under Mediterranean conditions - A. Abdelkhalik; B. Pascual; I. Nájera; M. A. Domene; C. Baixauli; N. Pascual-Seva (Irrigation Science, 2020)

Removal of carbamazepine, ciprofloxacin and ibuprofen in real urban wastewater by using light-driven advanced oxidation processes - A. Monteoliva-García; J. Martín-Pascual; M. M. Muñío; J. M. Poyatos (International Journal of Environmental Science and Technology, 2019)

In vitro culture of the endangered plant Eryngium viviparum as dual strategy for its ex situ conservation and source of bioactive compounds - Manuel Ayuso; Pascual García-Pérez; Pablo Ramil-Rego; Pedro Pablo Gallego; M. Esther Barreal (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Maternal influence on early lipid content in an introduced partially anadromous population of Oncorhynchus mykiss - Ana L. Liberoff; Alejandra A. Leal; María E. Díaz De Vivar; Carla M. Riva‐Rossi; Miguel A. Pascual (Journal of Fish Biology, 2019)
This study evaluated how the maternal migratory tactic in a partially anadromous population of Oncorhynchus mykiss may influence the early energetic status of their offspring. Total lipid content variation (% dry mass) of recently emerged fry caught in the Santa Cruz River, Argentina, was evaluated as a function of their maternal origin (anadromous v . resident) and fork length ( L F ). Lipid content of fry decreased with L F and was higher for offspring of anadromous mothers.

Correction to: STIM1 deficiency is linked to Alzheimer’s disease and triggers cell death in SH-SY5Y cells by upregulation of L-type voltage-operated Ca2+ entry - Carlos Pascual-Caro; Maria Berrocal; Aida M. Lopez-Guerrero; Alberto Alvarez-Barrientos; Eulalia Pozo-Guisado; Carlos Gutierrez-Merino; Ana M. Mata; Francisco Javier Martin-Romero (Journal of Molecular Medicine, 2019)

In Memoriam: Fernando Lopes da Silva (1935–2019) - Christoph M. Michel; Sylvain Baillet; Christian Benar; Olivier Bertrand; Jean Gotman; Bin He; Geert-Jan Huiskamp; Louis Lemieux; Scott Makeig; Alvaro Pascual-Leone; Riitta Salmelin; Stefano Seri; et al. (Brain Topography, 2019)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Large birds travel farther in homogeneous environments - Marlee A. Tucker; Olga Alexandrou; Richard O. Bierregaard; Keith L. Bildstein; Katrin Böhning‐Gaese; Chloe Bracis; John N. Brzorad; Evan R. Buechley; David Cabot; Justin M. Calabrese; Carlos Carrapato; Andre Chiaradia; et al. (Global Ecology and Biogeography, 2019)
Aim Animal movement is an important determinant of individual survival, population dynamics and ecosystem structure and function. Nonetheless, it is still unclear how local movements are related to resource availability and the spatial arrangement of resources. Using resident bird species and migratory bird species outside the migratory period, we examined how the distribution of resources affects the movement patterns of both large terrestrial birds (e.g., raptors, bustards and hornbills) and waterbirds (e.g., cranes, storks, ducks, geese and flamingos). Location Global. Time period 2003–2015. Major taxa studied Birds. Methods We compiled GPS tracking data for 386 individuals across 36 bird species. We calculated the straight‐line distance between GPS locations of each individual at the 1‐hr and 10‐day time‐scales. For each individual and time‐scale, we calculated the median and 0.95 quantile of displacement. We used linear mixed‐effects models to examine the effect of the spatial arrangement of resources, measured as enhanced vegetation index homogeneity, on avian movements, while accounting for mean resource availability, body mass, diet, flight type, migratory status and taxonomy and spatial autocorrelation. Results We found a significant effect of resource spatial arrangement at the 1‐hr and 10‐day time‐scales. On average, individual movements were seven times longer in environments with homogeneously distributed resources compared with areas of low resource homogeneity. Contrary to previous work, we found no significant effect of resource availability, diet, flight type, migratory status or body mass on the non‐migratory movements of birds. Main conclusions We suggest that longer movements in homogeneous environments might reflect the need for different habitat types associated with foraging and reproduction. This highlights the importance of landscape complementarity, where habitat patches within a landscape include a range of different, yet complementary resources. As habitat homogenization increases, it might force birds to travel increasingly longer distances to meet their diverse needs.

Frontiers in Fine-Scale in situ Studies: Opportunities During the SWOT Fast Sampling Phase - Francesco d’Ovidio; Ananda Pascual; Jinbo Wang; Andrea M. Doglioli; Zhao Jing; Sebastien Moreau; Gérald Grégori; Sebastiaan Swart; Sabrina Speich; Frédéric Cyr; Benoit Legresy; Yi Chao; et al. (Frontiers in Marine Science, 2019)

How many came home? Evaluating ex situ conservation of green turtles in the Cayman Islands - Anna Barbanti; Clara Martin; Janice M. Blumenthal; Jack Boyle; Annette C. Broderick; Lucy Collyer; Gina Ebanks‐Petrie; Brendan J. Godley; Walter Mustin; Víctor Ordóñez; Marta Pascual; Carlos Carreras (Molecular Ecology, 2019)
Ex situ management is an important conservation tool that allows the preservation of biological diversity outside natural habitats while supporting survival in the wild. Captive breeding followed by re‐introduction is a possible approach for endangered species conservation and preservation of genetic variability. The Cayman Turtle Centre Ltd was established in 1968 to market green turtle ( Chelonia mydas ) meat and other products and replenish wild populations, thought to be locally extirpated, through captive breeding. We evaluated the effects of this re‐introduction programmme using molecular markers (13 microsatellites, 800‐bp D‐loop and simple tandem repeat mitochondrial DNA sequences) from captive breeders ( N = 257) and wild nesting females ( N = 57) (sampling period: 2013–2015). We divided the captive breeders into three groups: founders (from the original stock), and then two subdivisions of F 1 individuals corresponding to two different management strategies, cohort 1995 (“C1995”) and multicohort F 1 (“MCF1”). Loss of genetic variability and increased relatedness was observed in the captive stock over time. We found no significant differences in diversity among captive and wild groups, and similar or higher levels of haplotype variability when compared to other natural populations. Using parentage and sibship assignment, we determined that 90% of the wild individuals were related to the captive stock. Our results suggest a strong impact of the re‐introduction programmme on the present recovery of the wild green turtle population nesting in the Cayman Islands. Moreover, genetic relatedness analyses of captive populations are necessary to improve future management actions to maintain genetic diversity in the long term and avoid inbreeding depression.

Range, population structure and morphological characterization of the small range endemic bush-cricket Lluciapomaresius panteli (Orthoptera: Tettigoniidae: Bradyporinae) - J. Solé; M. A. Arnedo; J. Barat; A. Enguídanos; J. Pujade-Villar; M. Franch; O. Cadiach; F. Aguilar; G. García; R. Pascual (Journal of Insect Conservation, 2018)

Wheat grains fermented by fungal mycelia (Pleurotus ostreatus or Lentinus edodes) as alternative feed ingredients for juvenile rainbow trout (Oncorhynchus mykiss) - Mariano M. Pascual; Juan P. Hualde; Virginia A. Bianchi; Pablo Moreno; Juan M. Castro; Carlos M. Luquet (Aquaculture International, 2018)

Framing natural assets for advancing sustainability research: translating different perspectives into actions - Maria Jose Martinez-Harms; Stefan Gelcich; Rainer M. Krug; Fleur J. F. Maseyk; Hannah Moersberger; Archi Rastogi; Geoffrey Wambugu; Cornelia B. Krug; Eva M. Spehn; Unai Pascual (Sustainability Science, 2018)
Sustainability is a key challenge for humanity in the context of complex and unprecedented global changes. Future Earth, an international research initiative aiming to advance global sustainability science, has recently launched knowledge–action networks (KANs) as mechanisms for delivering its research strategy. The research initiative is currently developing a KAN on “natural assets” to facilitate and enable action-oriented research and synthesis towards natural assets sustainability. ‘Natural assets’ has been adopted by Future Earth as an umbrella term aiming to translate and bridge across different knowledge systems and different perspectives on peoples’ relationships with nature. In this paper, we clarify the framing of Future Earth around natural assets emphasizing the recognition on pluralism and identifying the challenges of translating different visions about the role of natural assets, including via policy formulation, for local to global sustainability challenges. This understanding will be useful to develop inter-and transdisciplinary solutions for human–environmental problems by (i) embracing richer collaborative decision processes and building bridges across different perspectives; (ii) giving emphasis on the interactions between biophysical and socioeconomic drivers affecting the future trends of investments and disinvestments in natural assets; and (iii) focusing on social equity, power relationships for effective application of the natural assets approach. This understanding also intends to inform the scope of the natural asset KAN’s research agenda to mobilize the translation of research into co-designed action for sustainability.

Distinct patterns of exocytosis elicited by Ca2+, Sr2+ and Ba2+ in bovine chromaffin cells - Andrés M. Baraibar; Ricardo de Pascual; Marcial Camacho; Natalia Domínguez; J. David Machado; Luis Gandía; Ricardo Borges (Pflügers Archiv - European Journal of Physiology, 2018)

STIM1 deficiency is linked to Alzheimer’s disease and triggers cell death in SH-SY5Y cells by upregulation of L-type voltage-operated Ca2+ entry - Carlos Pascual-Caro; Maria Berrocal; Aida M. Lopez-Guerrero; Alberto Alvarez-Barrientos; Eulalia Pozo-Guisado; Carlos Gutierrez-Merino; Ana M. Mata; Francisco Javier Martin-Romero (Journal of Molecular Medicine, 2018)
STIM1 is an endoplasmic reticulum protein with a role in Ca 2+ mobilization and signaling. As a sensor of intraluminal Ca 2+ levels, STIM1 modulates plasma membrane Ca 2+ channels to regulate Ca 2+ entry. In neuroblastoma SH-SY5Y cells and in familial Alzheimer’s disease patient skin fibroblasts, STIM1 is cleaved at the transmembrane domain by the presenilin-1-associated γ-secretase, leading to dysregulation of Ca 2+ homeostasis. In this report, we investigated expression levels of STIM1 in brain tissues (medium frontal gyrus) of pathologically confirmed Alzheimer’s disease patients, and observed that STIM1 protein expression level decreased with the progression of neurodegeneration. To study the role of STIM1 in neurodegeneration, a strategy was designed to knock-out the expression of STIM1 gene in the SH-SY5Y neuroblastoma cell line by CRISPR/Cas9-mediated genome editing, as an in vitro model to examine the phenotype of STIM1-deficient neuronal cells. It was proved that, while STIM1 is not required for the differentiation of SH-SY5Y cells, it is absolutely essential for cell survival in differentiating cells. Differentiated STIM1-KO cells showed a significant decrease of mitochondrial respiratory chain complex I activity, mitochondrial inner membrane depolarization, reduced mitochondrial free Ca 2+ concentration, and higher levels of senescence as compared with wild-type cells. In parallel, STIM1-KO cells showed a potentiated Ca 2+ entry in response to depolarization, which was sensitive to nifedipine, pointing to L-type voltage-operated Ca 2+ channels as mediators of the upregulated Ca 2+ entry. The stable knocking-down of CACNA1C transcripts restored mitochondrial function, increased mitochondrial Ca 2+ levels, and dropped senescence to basal levels, demonstrating the essential role of the upregulation of voltage-operated Ca 2+ entry through Ca v 1.2 channels in STIM1-deficient SH-SY5Y cell death. Key messages STIM1 protein expression decreases with the progression of neurodegeneration in Alzheimer’s disease. STIM1 is essential for cell viability in differentiated SH-SY5Y cells. STIM1 deficiency triggers voltage-regulated Ca 2+ entry-dependent cell death. Mitochondrial dysfunction and senescence are features of STIM1-deficient differentiated cells.

Hydrogen sulphide facilitates exocytosis by regulating the handling of intracellular calcium by chromaffin cells - Ricardo de Pascual; Andrés M. Baraibar; Iago Méndez-López; Martín Pérez-Ciria; Ignacio Polo-Vaquero; Luis Gandía; Sunny E. Ohia; Antonio G. García; Antonio M. G. de Diego (Pflügers Archiv - European Journal of Physiology, 2018)

Age estimation of the oyster Ostrea puelchana determined from the hinge internal growth pattern - M. S. Doldan; M. de Rafélis; M. A. Kroeck; M. S. Pascual; E. M. Morsan (Marine Biology, 2018)

First Steps towards the Pharmaceutical Development of Ovules Containing Lactobacillus Strains: Viability and Antimicrobial Activity as Basic First Parameters in Vaginal Formulations - A. L. Camilletti; F. O. Ruíz; L. M. Pascual; I. L. Barberis (AAPS PharmSciTech, 2018)

Effect of a 2000-m running test on antioxidant and cytokine response in plasma and circulating cells - Lucrecia Carrera-Quintanar; Lorena Funes; Miguel Sánchez-Martos; Pascual Martinez-Peinado; José M. Sempere; Antoni Pons; Vicente Micol; Enrique Roche (Journal of Physiology and Biochemistry, 2017)

White-gutted soldiers: simplification of the digestive tube for a non-particulate diet in higher Old World termites (Isoptera: Termitidae) - R. H. Scheffrahn; T. Bourguignon; C. Bordereau; R. A. Hernandez-Aguilar; V. M. Oelze; P. Dieguez; J. Šobotnik; A. Pascual-Garrido (Insectes Sociaux, 2017)

Microsporidians xenomas of anglerfish from NE A tlantic waters - M Llarena‐Reino; E Abollo; S Pascual (Journal of Fish Diseases, 2017)
The presence of emergent visible parasites at commercial valuable fish species is increasingly causing problems at fisheries and seafood industries. Microsporidians have been previously reported to appear forming apparent xenomas complexes in anglerfish species, but no effort has been carried out to simultaneously integrate epidemiological data, phenotypic, genotypic and fine structural characterizations in the same parasite sample. In this work, specimens of Lophius budegassa and Lophius piscatorius from NE Atlantic waters were sampled and examined to provide information about specific site of infection and demographic data of two groups of different sizes of xenomas present at both fish species. Histological descriptions and scanning and transmission electron microscopy were carried out on fresh spores of Lophius budegassa for ultrastructural studies. In both types of xenomas, it was observed simultaneously the microsporidian genus Spraguea in the form of two different types of spores. Molecular analyses of both xenomas from the two fish species, based on the small subunit ribosomal DNA gene, were also performed to genetically support the morphological diagnostic provided.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Diet supplemented with Grifola gargal mushroom enhances growth, lipid content, and nutrient retention of juvenile rainbow trout (Oncorhynchus mykiss) - Mariano M. Pascual; Juan P. Hualde; Virginia A. Bianchi; Juan M. Castro; Carlos M. Luquet (Aquaculture International, 2017)

EEG Microstate Correlates of Fluid Intelligence and Response to Cognitive Training - Emiliano Santarnecchi; Arjun R. Khanna; Christian S. Musaeus; Christopher S. Y. Benwell; Paula Davila; Faranak Farzan; Santosh Matham; Alvaro Pascual-Leone; Mouhsin M. Shafi (Brain Topography, 2017)

Age-dependent changes of cerebral copper metabolism in Atp7b −/− knockout mouse model of Wilson’s disease by [64Cu]CuCl2-PET/CT - Fang Xie; Yin Xi; Juan M. Pascual; Otto Muzik; Fangyu Peng (Metabolic Brain Disease, 2017)

Moving bed biofilm reactor to treat wastewater - J. C. Leyva-Díaz; J. Martín-Pascual; J. M. Poyatos (International Journal of Environmental Science and Technology, 2017)

Role of the polycarboxylic compounds in the response of Silene vulgaris to chromium - Ana E. Pradas del Real; Jose Manuel Silvan; Sonia de Pascual-Teresa; Ana Guerrero; Pilar García-Gonzalo; M. Carmen Lobo; Araceli Pérez-Sanz (Environmental Science and Pollution Research, 2017)

Spatial-depth functional estimation of ocean temperature from non-separable covariance models - R. M. Espejo; R. Fernández-Pascual; M. D. Ruiz-Medina (Stochastic Environmental Research and Risk Assessment, 2017)

Bloodstream infections caused by Escherichia coli producing AmpC β-lactamases: epidemiology and clinical features - V. Pascual; N. Alonso; M. Simó; G. Ortiz; M. C. Garcia; M. Xercavins; A. Rivera; M. A. Morera; E. Miró; E. Espejo; F. Navarro; M. Gurguí; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Reproductive strategy of common dentex Dentex dentex: management implications - A. GRAU; F. SABORIDO-REY; E. PASTOR; M. PALMER; E. MASSUTÍ-PASCUAL; A. QUETGLAS; I. RIERA; B. MORALES-NIN (Mediterranean Marine Science, 2016)
Common dentex Dentex dentex is an iconic endangered species in the Mediterranean where is a sought after target species for small-scale, recreational and spearfishing fisheries. The reproductive biology of D. dentex in the natural environment is poorly known; therefore the reproductive strategy of the species was assessed by combining reproductive traits with the growth characteristics (estimated from length-at-age data), the size/age of sexual maturity and the energetic dynamics. A total of 358 wild fish were sampled on Mallorca Island (W Mediterranean) from March 1996 to June 1999 with a 19 to 84.7 cm total length (LT) range. The sex ratio was skewed towards females (1.361) albeit the length composition was not different between sexes (p = 0.551). Three young immature individuals (

Biaxial Mechanical Evaluation of Absorbable and Nonabsorbable Synthetic Surgical Meshes Used for Hernia Repair: Physiological Loads Modify Anisotropy Response - A. Cordero; B. Hernández-Gascón; G. Pascual; J. M. Bellón; B. Calvo; E. Peña (Annals of Biomedical Engineering, 2016)

Drosophila as models to understand the adaptive process during invasion - Patricia Gibert; Matthew Hill; Marta Pascual; Christophe Plantamp; John S. Terblanche; Amir Yassin; Carla M. Sgrò (Biological Invasions, 2016)

Pharmacological Interventions to Ameliorate Neuropathological Symptoms in a Mouse Model of Lafora Disease - Arnaud Berthier; Miguel Payá; Ana M. García-Cabrero; Maria Inmaculada Ballester; Miguel Heredia; José M. Serratosa; Marina P. Sánchez; Pascual Sanz (Molecular Neurobiology, 2016)

Moment and Bayesian wavelet regression from spatially correlated functional data - R. M. Fernández-Pascual; R. Espejo; M. D. Ruiz-Medina (Stochastic Environmental Research and Risk Assessment, 2016)

Kinetic modelling of TOC removal by H2O2/UV, photo-Fenton and heterogeneous photocatalysis processes to treat dye-containing wastewater - C. Lopez-Lopez; J. Martín-Pascual; M. V. Martínez-Toledo; M. M. Muñío; E. Hontoria; J. M. Poyatos (International Journal of Environmental Science and Technology, 2015)

The SARAL/AltiKa Altimetry Satellite Mission - Jacques Verron; Pierre Sengenes; Juliette Lambin; Jocelyne Noubel; Nathalie Steunou; Amandine Guillot; Nicolas Picot; Sophie Coutin-Faye; Rashmi Sharma; R. M. Gairola; D. V. A. Raghava Murthy; James G. Richman; et al. (Marine Geodesy, 2015)

Impact of intermittent hypoxia and exercise on blood pressure and metabolic features from obese subjects suffering sleep apnea-hypopnea syndrome - P. González-Muniesa; A. Lopez-Pascual; J. de Andrés; A. Lasa; M. P. Portillo; F. Arós; J. Durán; C. J. Egea; J. A. Martinez (Journal of Physiology and Biochemistry, 2015)

Invasion biology of spotted wing Drosophila (Drosophila suzukii): a global perspective and future priorities - Mark K. Asplen; Gianfranco Anfora; Antonio Biondi; Deuk-Soo Choi; Dong Chu; Kent M. Daane; Patricia Gibert; Andrew P. Gutierrez; Kim A. Hoelmer; William D. Hutchison; Rufus Isaacs; Zhi-Lin Jiang; et al. (Journal of Pest Science, 2015)

Impact of borderline minimum inhibitory concentration on the outcome of invasive infections caused by Enterobacteriaceae treated with β-lactams: a systematic review and meta-analysis - E. Torres; M. Delgado; A. Valiente; Á. Pascual; J. Rodríguez-Baño (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Dams versus habitat: predicting the effects of dams on habitat supply and juvenile rainbow trout along the Santa Cruz River, Patagonia - Analía P. Quiroga; Julio L. Lancelotti; Carla M. Riva-Rossi; Marina Tagliaferro; Martin García Asorey; Miguel A. Pascual (Hydrobiologia, 2015)

Effects of alternate wetting and drying (AWD) threshold level and plant seedling age on crop performance, water input, and water productivity of transplanted rice in Central Luzon, Philippines - R. M. Lampayan; K. C. Samoy-Pascual; E. B. Sibayan; V. B. Ella; O. P. Jayag; R. J. Cabangon; B. A. M. Bouman (Paddy and Water Environment, 2015)

Ongoing expansion of the worldwide invader Didemnum vexillum (Ascidiacea) in the Mediterranean Sea: high plasticity of its biological cycle promotes establishment in warm waters - V. Ordóñez; M. Pascual; M. Fernández-Tejedor; M. C. Pineda; D. Tagliapietra; X. Turon (Biological Invasions, 2015)

Sun Protection Among Spanish Beachgoers: Knowledge, Attitude and Behaviour - M. C. Cercato; V. Ramazzotti; I. Sperduti; A. Asensio-Pascual; I. Ribes; C. Guillén; E. Nagore (Journal of Cancer Education, 2015)

Small Mammals Along SW-Atlantic Marshes: Diversity Correlates with Inland Habitats but Abundance Correlates with Marsh Characteristics - Alejandro D. Canepuccia; Jesús Pascual; Laura M. Biondi; Oscar O. Iribarne (Wetlands, 2015)

Isolation and molecular identification of the scuticociliate P orpostoma notata Moebius, 1888 from moribund reared H ippocampus hippocampus (L.) seahorses, by amplification of the SSU rRNA gene sequences - C Ofelio; A Blanco; Á Roura; J Pintado; S Pascual; M Planas (Journal of Fish Diseases, 2014)

Computation of a new mean dynamic topography for the Mediterranean Sea from model outputs, altimeter measurements and oceanographic in situ data - M.-H. Rio; A. Pascual; P.-M. Poulain; M. Menna; B. Barceló; J. Tintoré (Ocean Science, 2014)
The accurate knowledge of the ocean's mean dynamic topography (MDT) is a crucial issue for a number of oceanographic applications and, in some areas of the Mediterranean Sea, important limitations have been found pointing to the need of an upgrade. We present a new MDT that was computed for the Mediterranean Sea. It profits from improvements made possible by the use of extended data sets and refined processing. The updated data set spans the 1993–2012 period and consists of drifter velocities, altimetry data, hydrological profiles and model data. The methodology is similar to the previous MDT by Rio et al. (2007). However, in Rio et al. (2007) no hydrological profiles had been taken into account. This required the development of dedicated processing. A number of sensitivity studies have been carried out to obtain the most accurate MDT as possible. The main results from these sensitivity studies are the following: moderate impact to the choice of correlation scales but almost negligible sensitivity to the choice of the first guess (model solution). A systematic external validation to independent data has been made to evaluate the performance of the new MDT. Compared to previous versions, SMDT-MED-2014 (Synthetic Mean Dynamic Topography of the MEDiterranean sea) features shorter-scale structures, which results in an altimeter velocity variance closer to the observed velocity variance and, at the same time, gives better Taylor skills.

Influence of hydraulic retention time on heterotrophic biomass in a wastewater moving bed membrane bioreactor treatment plant - J. Martín-Pascual; P. Reboleiro-Rivas; C. López-López; J. González-López; E. Hontoria; J. M. Poyatos (International Journal of Environmental Science and Technology, 2014)

Physical forcing and physical/biochemical variability of the Mediterranean Sea: a review of unresolved issues and directions for future research - P. Malanotte-Rizzoli; V. Artale; G. L. Borzelli-Eusebi; S. Brenner; A. Crise; M. Gacic; N. Kress; S. Marullo; M. Ribera d'Alcalà; S. Sofianos; T. Tanhua; A. Theocharis; et al. (Ocean Science, 2014)
This paper is the outcome of a workshop held in Rome in November 2011 on the occasion of the 25th anniversary of the POEM (Physical Oceanography of the Eastern Mediterranean) program. In the workshop discussions, a number of unresolved issues were identified for the physical and biogeochemical properties of the Mediterranean Sea as a whole, i.e., comprising the Western and Eastern sub-basins. Over the successive two years, the related ideas were discussed among the group of scientists who participated in the workshop and who have contributed to the writing of this paper. Three major topics were identified, each of them being the object of a section divided into a number of different sub-sections, each addressing a specific physical, chemical or biological issue: 1. Assessment of basin-wide physical/biochemical properties, of their variability and interactions. 2. Relative importance of external forcing functions (wind stress, heat/moisture fluxes, forcing through straits) vs. internal variability. 3. Shelf/deep sea interactions and exchanges of physical/biogeochemical properties and how they affect the sub-basin circulation and property distribution. Furthermore, a number of unresolved scientific/methodological issues were also identified and are reported in each sub-section after a short discussion of the present knowledge. They represent the collegial consensus of the scientists contributing to the paper. Naturally, the unresolved issues presented here constitute the choice of the authors and therefore they may not be exhaustive and/or complete. The overall goal is to stimulate a broader interdisciplinary discussion among the scientists of the Mediterranean oceanographic community, leading to enhanced collaborative efforts and exciting future discoveries.

Genetic structure of a phytophagous mite species affected by crop practices: the case of Tetranychus urticae in clementine mandarins - S. Pascual-Ruiz; M. A. Gómez-Martinez; T. Ansaloni; J. G. Segarra-Moragues; B. Sabater-Muñoz; J. A. Jacas; M. A. Hurtado-Ruiz (Experimental and Applied Acarology, 2014)

Preclinical PK/PD modeling and human efficacious dose projection for a glucokinase activator in the treatment of diabetes - Michael G. Zager; Kirk Kozminski; Bernadette Pascual; Kathleen M. Ogilvie; Shaoxian Sun (Journal of Pharmacokinetics and Pharmacodynamics, 2014)

Economic threshold for Tetranychus urticae (Acari: Tetranychidae) in clementine mandarins Citrus clementina - Sara Pascual-Ruiz; Ernestina Aguilar-Fenollosa; Victoria Ibáñez-Gual; Mónica A. Hurtado-Ruiz; M. Teresa Martínez-Ferrer; Josep A. Jacas (Experimental and Applied Acarology, 2014)

Compliance with quality prescribing indicators linked to financial incentives: what about not incentivized indicators?: an observational study - R. Fernández Urrusuno; P. Pérez Pérez; M. C. Montero Balosa; C. Márquez Calzada; B. Pascual de la Pisa (European Journal of Clinical Pharmacology, 2014)

Modulation of EEG Functional Connectivity Networks in Subjects Undergoing Repetitive Transcranial Magnetic Stimulation - Mouhsin M. Shafi; M. Brandon Westover; Lindsay Oberman; Sydney S. Cash; Alvaro Pascual-Leone (Brain Topography, 2014)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

The physiology of ex vitro pineapple (Ananas comosus L. Merr. var MD-2) as CAM or C3 is regulated by the environmental conditions: proteomic and transcriptomic profiles - C. Aragón; P. Pascual; J. González; M. Escalona; L. Carvalho; S. Amancio (Plant Cell Reports, 2013)

Addressing a critique of the TEASI framework for invasive species risk assessment - Brian Leung; Nuria Roura‐Pascual; Sven Bacher; Jaakko Heikkilä; Lluis Brotons; Mark A Burgman; Katharina Dehnen‐Schmutz; Franz Essl; Philip E Hulme; David M Richardson; Daniel Sol; Montserrat Vilà (Ecology Letters, 2013)
We address criticism that the Transport, Establishment, Abundance, Spread, Impact (TEASI) framework does not facilitate objective mapping of risk assessment methods nor defines best practice. We explain why TEASI is appropriate for mapping, despite inherent challenges, and how TEASI offers considerations for best practices, rather than suggesting one best practice.

Cerebellar TMS in Treatment of a Patient with Cerebellar Ataxia: Evidence from Clinical, Biomechanics and Neurophysiological Assessments - Faranak Farzan; Yunfen Wu; Brad Manor; Elana M. Anastasio; Matthew Lough; Vera Novak; Patricia E. Greenstein; Alvaro Pascual-Leone (The Cerebellum, 2013)

Effect of the Operative Variables on the Treatment of Wastewater Polluted with Phthalo Blue by H2O2/UV Process - C. Lopez-Lopez; J. Martín-Pascual; M. V. Martínez-Toledo; J. González-López; E. Hontoria; J. M. Poyatos (Water, Air, & Soil Pollution, 2013)

Lung cancer risk associated with residential proximity to industrial installations: a spatial analysis - M. F. López-Cima; J. García-Pérez; B. Pérez-Gómez; N. Aragonés; G. López-Abente; T. Pascual; A. Tardón; M. Pollán (International Journal of Environmental Science and Technology, 2013)

Shifts in δ 15 N signature following the onset of exogenous feeding in rainbow trout Oncorhynchus mykiss : importance of combining length and age data - A. L. Liberoff; C. M. Riva Rossi; M. L. Fogel; J. E. Ciancio; M. A. Pascual (Journal of Fish Biology, 2013)
The δ 15 N isotopic change of recently emerged rainbow trout Oncorhynchus mykiss due to diet shift from yolk sac to exogenous feeding was evaluated in a field study. The fit of a general model including both fish length and age in days as co‐variables indicates that the specific δ 15 N of individual fish at any given time along the ontogeny is determined by its growth trajectory. The results suggest that estimations based on fish size alone could bias data interpretation and maternal origin determinations in partially migratory salmonids.

Erratum to: Prevalence and molecular epidemiology of acquired AmpC β-lactamases and carbapenemases in Enterobacteriaceae isolates from 35 hospitals in Spain - E. Miró; J. Agüero; M. N. Larrosa; A. Fernández; M. C. Conejo; G. Bou; J. J. González-López; N. Lara; L. Martínez-Martínez; A. Oliver; B. Aracil; J. Oteo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Prevalence and molecular epidemiology of acquired AmpC β-lactamases and carbapenemases in Enterobacteriaceae isolates from 35 hospitals in Spain - E. Miró; J. Agüero; M. N. Larrosa; A. Fernández; M. C. Conejo; G. Bou; J. J. González-López; N. Lara; L. Martínez-Martínez; A. Oliver; B. Aracil; J. Oteo; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Optimal integration of gaseous emissions from new industrial plants with the surroundings - Pascual Eduardo Murillo-Alvarado; José María Ponce-Ortega; Mahmoud M. El-Halwagi; Juan Gabriel Segovia-Hernandez (Clean Technologies and Environmental Policy, 2013)

Understanding the Passive Mechanical Behavior of the Human Abdominal Wall - B. Hernández-Gascón; A. Mena; E. Peña; G. Pascual; J. M. Bellón; B. Calvo (Annals of Biomedical Engineering, 2013)

The invasion of Patagonia by Chinook salmon (Oncorhynchus tshawytscha): inferences from mitochondrial DNA patterns - C. M. Riva Rossi; M. A. Pascual; E. Aedo Marchant; N. Basso; J. E. Ciancio; B. Mezga; D. A. Fernández; B. Ernst-Elizalde (Genetica, 2012)

Identification, molecular characterisation and antimicrobial susceptibility of genomovars of the Burkholderia cepacia complex in Spain - M. J. Medina-Pascual; S. Valdezate; P. Villalón; N. Garrido; V. Rubio; J. A. Saéz-Nieto (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

TEASIng apart alien species risk assessments: a framework for best practices - Brian Leung; Nuria Roura‐Pascual; Sven Bacher; Jaakko Heikkilä; Lluis Brotons; Mark A. Burgman; Katharina Dehnen‐Schmutz; Franz Essl; Philip E. Hulme; David M. Richardson; Daniel Sol; Montserrat Vilà (Ecology Letters, 2012)
Some alien species cause substantial impacts, yet most are innocuous. Given limited resources, forecasting risks from alien species will help prioritise management. Given that risk assessment ( RA ) approaches vary widely, a synthesis is timely to highlight best practices. We reviewed quantitative and scoring RA s, integrating > 300 publications into arguably the most rigorous quantitative RA framework currently existing, and mapping each study onto our framework, which combines Transport, Establishment, Abundance, Spread and Impact ( TEASI ). Quantitative models generally measured single risk components (78% of studies), often focusing on Establishment alone (79%). Although dominant in academia, quantitative RA s are underused in policy, and should be made more accessible. Accommodating heterogeneous limited data, combining across risk components, and developing generalised RA s across species, space and time without requiring new models for each species may increase attractiveness for policy applications. Comparatively, scoring approaches covered more risk components (50% examined > 3 components), with Impact being the most common component (87%), and have been widely applied in policy (> 57%), but primarily employed expert opinion. Our framework provides guidance for questions asked, combining scores and other improvements. Our risk framework need not be completely parameterised to be informative, but instead identifies opportunities for improvement in alien species RA .

Regulation by L-Type Calcium Channels of Endocytosis: An Overview - Juliana M. Rosa; Carmen Nanclares; Angela Orozco; Inés Colmena; Ricardo de Pascual; Antonio G. García; Luis Gandía (Journal of Molecular Neuroscience, 2012)

Aetiology of community-acquired pneumonia among adults in an H1N1 pandemic year: the role of respiratory viruses - A. Sangil; E. Calbo; A. Robles; S. Benet; M. E. Viladot; V. Pascual; E. Cuchí; J. Pérez; B. Barreiro; B. Sánchez; J. Torres; L. Canales; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Iterative species distribution modelling and ground validation in endemism research: an Alpine jumping bristletail example - Lukas J. Rinnhofer; Núria Roura-Pascual; Wolfgang Arthofer; Thomas Dejaco; Barbara Thaler-Knoflach; Gregor A. Wachter; Erhard Christian; Florian M. Steiner; Birgit C. Schlick-Steiner (Biodiversity and Conservation, 2012)

Carbon outcomes of major land‐cover transitions in SE Asia: great uncertainties and REDD + policy implications - Alan D. Ziegler; Jacob Phelps; Jia QI Yuen; Edward L. Webb; Deborah Lawrence; Jeff M. Fox; Thilde B. Bruun; Stephen J. Leisz; Casey M. Ryan; Wolfram Dressler; Ole Mertz; Unai Pascual; et al. (Global Change Biology, 2012)
Policy makers across the tropics propose that carbon finance could provide incentives for forest frontier communities to transition away from swidden agriculture (slash‐and‐burn or shifting cultivation) to other systems that potentially reduce emissions and/or increase carbon sequestration. However, there is little certainty regarding the carbon outcomes of many key land‐use transitions at the center of current policy debates. Our meta‐analysis of over 250 studies reporting above‐ and below‐ground carbon estimates for different land‐use types indicates great uncertainty in the net total ecosystem carbon changes that can be expected from many transitions, including the replacement of various types of swidden agriculture with oil palm, rubber, or some other types of agroforestry systems. These transitions are underway throughout Southeast Asia, and are at the heart of REDD + debates. Exceptions of unambiguous carbon outcomes are the abandonment of any type of agriculture to allow forest regeneration (a certain positive carbon outcome) and expansion of agriculture into mature forest (a certain negative carbon outcome). With respect to swiddening, our meta‐analysis supports a reassessment of policies that encourage land‐cover conversion away from these [especially long‐fallow] systems to other more cash‐crop‐oriented systems producing ambiguous carbon stock changes – including oil palm and rubber. In some instances, lengthening fallow periods of an existing swidden system may produce substantial carbon benefits, as would conversion from intensely cultivated lands to high‐biomass plantations and some other types of agroforestry. More field studies are needed to provide better data of above‐ and below‐ground carbon stocks before informed recommendations or policy decisions can be made regarding which land‐use regimes optimize or increase carbon sequestration. As some transitions may negatively impact other ecosystem services, food security, and local livelihoods, the entire carbon and noncarbon benefit stream should also be taken into account before prescribing transitions with ambiguous carbon benefits.

Prescreening bacterial colonies for bioactive molecules with Janus plates, a SBS standard double-faced microbial culturing system - Marina Sánchez-Hidalgo; Javier Pascual; Mercedes de la Cruz; Jesús Martín; Gary S. Kath; Janet M. Sigmund; Prakash Masurekar; Francisca Vicente; Olga Genilloud; Gerald F. Bills (Antonie van Leeuwenhoek, 2012)

Characterization of nine polymorphic microsatellite loci for the calcareous sponge Paraleucilla magna Klautau et al. 2004 introduced to the Mediterranean Sea - G. Agell; J. Frotscher; M. Guardiola; M. Pascual; M. J. Uriz (Conservation Genetics Resources, 2012)

Comparative Kinetic Study of Carrier Type in a Moving Bed System Applied to Organic Matter Removal in Urban Wastewater Treatment - J. Martín-Pascual; C. López-López; A. Cerdá; J. González-López; E. Hontoria; J. M. Poyatos (Water, Air, & Soil Pollution, 2012)

Isolation and characterization of polymorphic microsatellite markers in Tetranychus urticae and cross amplification in other Tetranychidae and Phytoseiidae species of economic importance - B. Sabater-Muñoz; S. Pascual-Ruiz; M. A. Gómez-Martínez; J. A. Jacas; M. A. Hurtado (Experimental and Applied Acarology, 2012)

Assessment of goods and services, vulnerability, and conservation status of European seabed biotopes: a stepping stone towards ecosystem-based marine spatial management - M. SALOMIDI; S. KATSANEVAKIS; A. BORJA; U. BRAECKMAN; D. DAMALAS; I. GALPARSORO; R. MIFSUD; S. MIRTO; M. PASCUAL; C. PIPITONE; M. RABAUT; V. TODOROVA; et al. (Mediterranean Marine Science, 2012)
The goal of ecosystem-based marine spatial management is to maintain marine ecosystems in a healthy, productive and resilient condition; hence, they can sustainably provide the needed goods and services for human welfare. However, the increasing pressures upon the marine realm threaten marine ecosystems, especially seabed biotopes, and thus a well-planned approach of managing use of marine space is essential to achieve sustainability. The relative value of seabed biotopes, evaluated on the basis of goods and services, is an important starting point for the spatial management of marine areas. Herein, 56 types of European seabed biotopes and their related goods, services, sensitivity issues, and conservation status were compiled, the latter referring to management and protection tools which currently apply for these biotopes at European or international level. Fishing activities, especially by benthic trawls, and marine pollution are the main threats to European seabed biotopes. Increased seawater turbidity, dredged sediment disposal, coastal constructions, biological invasions, mining, extraction of raw materials, shipping-related activities, tourism, hydrocarbon exploration, and even some practices of scientific research, also exert substantial pressure. Although some first steps have been taken to protect the European sea beds through international agreements and European and national legislation, a finer scale of classification and assessment of marine biotopes is considered crucial in shaping sound priorities and management guidelines towards the effective conservation and sustainability of European marine resources.

Drying Rate Measurements in Convection- and Diffusion-Driven Conditions on a Shaly Sandstone Using Nuclear Magnetic Resonance - Y. Peysson; M. Fleury; V. Blázquez-Pascual (Transport in Porous Media, 2011)

Matching genetics with oceanography: directional gene flow in a Mediterranean fish species - C. SCHUNTER; J. CARRERAS‐CARBONELL; E. MACPHERSON; J. TINTORÉ; E. VIDAL‐VIJANDE; A. PASCUAL; P. GUIDETTI; M. PASCUAL (Molecular Ecology, 2011)
Genetic connectivity and geographic fragmentation are two opposing mechanisms determining the population structure of species. While the first homogenizes the genetic background across populations the second one allows their differentiation. Therefore, knowledge of processes affecting dispersal of marine organisms is crucial to understand their genetic distribution patterns and for the effective management of their populations. In this study, we use genetic analyses of eleven microsatellites in combination with oceanographic satellite and dispersal simulation data to determine distribution patterns for Serranus cabrilla , a ubiquitous demersal broadcast spawner, in the Mediterranean Sea. Pairwise population F ST values ranged between −0.003 and 0.135. Two genetically distinct clusters were identified, with a clear division located between the oceanographic discontinuities at the Ibiza Channel (IC) and the Almeria‐Oran Front (AOF), revealing an admixed population in between. The Balearic Front (BF) also appeared to dictate population structure. Directional gene flow on the Spanish coast was observed as S. cabrilla dispersed from west to east over the AOF, from north to south on the IC and from south of the IC towards the Balearic Islands. Correlations between genetic and oceanographic data were highly significant. Seasonal changes in current patterns and the relationship between ocean circulation patterns and spawning season may also play an important role in population structure around oceanographic fronts.

Ureaplasma urealyticum and Mycoplasma hominis Sensitivity to Bacteriocins Produced by Two Lactobacilli Strains - M. Daniele; F. Ruiz; L. Pascual; L. Barberis (Current Microbiology, 2011)

Age-Related Changes in the Thickness of Cortical Zones in Humans - Scott M. McGinnis; Michael Brickhouse; Belen Pascual; Bradford C. Dickerson (Brain Topography, 2011)

Characterizing Brain Cortical Plasticity and Network Dynamics Across the Age-Span in Health and Disease with TMS-EEG and TMS-fMRI - Alvaro Pascual-Leone; Catarina Freitas; Lindsay Oberman; Jared C. Horvath; Mark Halko; Mark Eldaief; Shahid Bashir; Marine Vernet; Mouhshin Shafi; Brandon Westover; Andrew M. Vahabzadeh-Hagh; Alexander Rotenberg (Brain Topography, 2011)

Assessment of the presence of extended-spectrum beta-lactamase-producing Escherichia coli in eggshells and ready-to-eat products - P. Egea; L. López-Cerero; M. D. Navarro; J. Rodríguez-Baño; A. Pascual (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

From global to local genetic structuring in the red gorgonian Paramuricea clavata : the interplay between oceanographic conditions and limited larval dispersal - K. MOKHTAR‐JAMAÏ; M. PASCUAL; J.‐B. LEDOUX; R. COMA; J.‐P. FÉRAL; J. GARRABOU; D. AURELLE (Molecular Ecology, 2011)
Defining the scale of connectivity among marine populations and identifying the barriers to gene flow are tasks of fundamental importance for understanding the genetic structure of populations and for the design of marine reserves. Here, we investigated the population genetic structure at three spatial scales of the red gorgonian Paramuricea clavata (Cnidaria, Octocorallia), a key species dwelling in the coralligenous assemblages of the Mediterranean Sea. Colonies of P. clavata were collected from 39 locations across the Mediterranean Sea from Morocco to Turkey and analysed using microsatellite loci. Within three regions (Medes, Marseille and North Corsica), sampling was obtained from multiple locations and at different depths. Three different approaches (measures of genetic differentiation, Bayesian clustering and spatially explicit maximum‐difference algorithm) were used to determine the pattern of genetic structure. We identified genetic breaks in the spatial distribution of genetic diversity, which were concordant with oceanographic conditions in the Mediterranean Sea. We revealed a high level of genetic differentiation among populations and a pattern of isolation by distance across the studied area and within the three regions, underlining short effective larval dispersal in this species. We observed genetic differentiation among populations in the same locality dwelling at different depths, which may be explained by local oceanographic conditions and which may allow a process of local adaptation of the populations to their environment. We discuss the implications of our results for the conservation of the species, which is exposed to various threats.

Interaction between water and nitrogen management in peaches for processing - J. Rufat; X. Domingo; A. Arbonés; M. Pascual; J. M. Villar (Irrigation Science, 2011)

Erratum to: Managing biological invasions: charting courses to desirable futures in the Cape Floristic Region - Núria Roura-Pascual; David M. Richardson; R. Arthur Chapman; Tanja Hichert; Rainer M. Krug (Regional Environmental Change, 2011)

Managing biological invasions: charting courses to desirable futures in the Cape Floristic Region - Núria Roura-Pascual; David M. Richardson; R. Arthur Chapman; Tanja Hichert; Rainer M. Krug (Regional Environmental Change, 2011)

Single Pulse TMS-Induced Modulations of Resting Brain Neurodynamics Encoded in EEG Phase - Catherine Stamoulis; Lindsay M. Oberman; Elke Praeg; Shahid Bashir; Alvaro Pascual-Leone (Brain Topography, 2011)

Partial characterization of hepatopancreatic and extracellular digestive proteinases of wild and cultivated Octopus maya - R. Martínez; R. Sántos; A. Álvarez; G. Cuzón; L. Arena; M. Mascaró; C. Pascual; C. Rosas (Aquaculture International, 2011)

Springtime coupled modes of regional wind in the Iberian Peninsula and large‐scale variability patterns - M. L. Martín; F. Valero; A. Morata; M. Y. Luna; A. Pascual; D. Santos‐Muñoz (International Journal of Climatology, 2011)
This paper investigates the relationships between the Global Circulation Model (GCM)‐simulated 1000 hPa geopotential heights (taken from the ERA40 reanalysis) over the North Atlantic and the regional wind over the Iberian Peninsula for springtime (March to May). The main goal is to recognize the atmospheric circulation patterns linked to wind anomaly configurations. The method used for the downscaling is singular value decomposition (SVD). After applying a Monte Carlo approach to assess the statistical significance of the obtained modes, the SVD analysis highlighted that the covariability is dominated by three main large‐scale features of the atmospheric circulation over the North Atlantic: (1) a first mode that relates local wind to the Scandinavian pattern (SCAN), by which a blocking pattern is linked to below‐normal winds, (2) a second covariability mode associated with the North Atlantic Oscillation (NAO) pattern that correlates with wind over Iberia. An enhanced spring NAO pattern is related to positive (negative) wind correlations over the northern (southern) Iberia and (3) a third SVD mode that relates wind to the East Atlantic (EA) pattern promoting a dissimilar behaviour in the Iberian wind with positive (negative) wind correlations in the western (eastern) part of Iberia. To conclude, composite maps were built up to give an average circulation associated with coherent wind variability over Iberia. Copyright © 2010 Royal Meteorological Society

Local imipenem activity against Pseudomonas aeruginosa decreases in vivo in the presence of siliconized latex - C. Pichardo; M. C. Conejo; F. Docobo-Pérez; C. Velasco; R. López-Rojas; I. García; M. E. Pachón-Ibáñez; J. M. Rodríguez; J. Pachón; A. Pascual (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Clearing of invasive alien plants under different budget scenarios: using a simulation model to test efficiency - Rainer M. Krug; Núria Roura-Pascual; David M. Richardson (Biological Invasions, 2010)

The inverse niche model for food webs with parasites - Christopher P. Warren; Mercedes Pascual; Kevin D. Lafferty; Armand M. Kuris (Theoretical Ecology, 2010)

Characterization and developmental expression of a glutamate decarboxylase from maritime pine - Juan Jesús Molina-Rueda; María Belén Pascual; Francisco M. Cánovas; Fernando Gallardo (Planta, 2010)

The spread of the Argentine ant: environmental determinants and impacts on native ant communities - Núria Roura-Pascual; Josep M. Bas; Cang Hui (Biological Invasions, 2010)

The mussel Xenostrobus securis: a well-established alien invader in the Ria de Vigo (Spain, NE Atlantic) - S. Pascual; A. Villalba; E. Abollo; M. Garci; A. F. González; M. Nombela; D. Posada; A. Guerra (Biological Invasions, 2010)

Biallelic MYH germline mutations as cause of Muir-Torre syndrome - Carmen Guillén-Ponce; Adela Castillejo; Víctor M. Barberá; J. Carlos Pascual-Ramírez; Encarnación Andrada; M. Isabel Castillejo; Carla Guarinós; M. J. Molina-Garrido; Alfredo Carrato; J. L. Soto (Familial Cancer, 2010)

Spatiotemporal filtering from fractal spatial functional data sequence - M. D. Ruiz-Medina; R. Fernández-Pascual (Stochastic Environmental Research and Risk Assessment, 2010)

A moderate intake of phytosterols from habitual diet affects cholesterol metabolism - T. Sanclemente; I. Marques-Lopes; M. Fajó-Pascual; M. Cofán; E. Jarauta; E. Ros; J. Puzo; A. L. García-Otín (Journal of Physiology and Biochemistry, 2009)

Fosfomycin in a single dose versus a 7-day course of amoxicillin–clavulanate for the treatment of asymptomatic bacteriuria during pregnancy - A. Estebanez; R. Pascual; V. Gil; F. Ortiz; M. Santibáñez; C. Pérez Barba (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Nicotine-conditioned place preference induced CREB phosphorylation and Fos expression in the adult rat brain - Mariano M. Pascual; Veronica Pastor; Ramon O. Bernabeu (Psychopharmacology, 2009)

Antimicrobial Activity, Inhibition of Urogenital Pathogens, and Synergistic Interactions Between Lactobacillus Strains - Francisco O. Ruiz; Gisela Gerbaldo; Paula Asurmendi; Liliana M. Pascual; Walter Giordano; Isabel L. Barberis (Current Microbiology, 2009)

Evaluation of Microbial Community Activity, Abundance and Structure in a Semiarid Soil Under Cadmium Pollution at Laboratory Level - Margarita Ros; Jose Antonio Pascual; Jose Luis Moreno; M. Teresa Hernandez; Carlos Garcia (Water, Air, & Soil Pollution, 2009)

A Quantitative Climate-Match Score for Risk-Assessment Screening of Reptile and Amphibian Introductions - Nicola J. van Wilgen; Núria Roura-Pascual; David M. Richardson (Environmental Management, 2009)

From introduction to equilibrium: reconstructing the invasive pathways of the Argentine ant in a Mediterranean region - NÚRIA ROURA‐PASCUAL; JOSEP M. BAS; WILFRIED THUILLER; CANG HUI; RAINER M. KRUG; LLUÍS BROTONS (Global Change Biology, 2009)
Determining the geographical range of invasive species is an important component of formulating effective management strategies. In the absence of detailed distributional data, species distribution models can provide estimates of an invasion range and increase our understanding of the ecological processes acting at various spatial scales. We used two complementary approaches to evaluate the influence of historical and environmental factors in shaping the distribution of the Argentine ant ( Linepithema humile ), a widespread, highly invasive species native to South America. Occurrence data were combined with environmental data at incremental spatial scales (extent and resolution) to predict the suitable range of the ant invasion using ecological niche models. In addition, we also used a spread model that simulated the jump dispersal of the species to identify the most plausible scenarios of arrival of L. humile in the NE Iberian Peninsula at local scales. Based on the results of both modelling practices, we suggest that L. humile might have reached its maximum geographic range at regional scales in the NE Iberian Peninsula. However, the species does not appear in equilibrium with the environment at small spatial scales, and further expansions are expected along coastal and inland localities of the Costa Brava. Long‐distance jumps are ultimately responsible for the spread of the Argentine ant in the area. Overall, our study shows the utility of combining niche based models with spread models to understand the dynamics of species' invasions.

Growth, yield and physiology of Verticillium-inoculated pepper plants treated with ATAD and composted sewage sludge - I. Pascual; I. Azcona; F. Morales; J. Aguirreolea; M. Sánchez-Díaz (Plant and Soil, 2009)

Contents of total protein, L-canavanine and condensed tannins of the one-flowered vetch (Vicia articulata Hornem.) collection of the Bank of Plant Germplasm of Cuenca (Spain) - R. Sánchez Vioque; I. Cantón Prado; F. Flores Gil; M. J. Giménez Alvear; M. De los Mozos Pascual; M. F. Rodríguez Conde (Genetic Resources and Crop Evolution, 2008)

Effect of sanitized and non-sanitized sewage sludge on soil microbial community and the physiology of pepper plants - I. Pascual; M. Avilés; J. Aguirreolea; M. Sánchez-Díaz (Plant and Soil, 2008)

Columnar cacti-shrub relationships in an Andean semiarid valley in western Venezuela - Daniel M. Larrea-Alcázar; Pascual J. Soriano (Plant Ecology, 2008)

Parasites in food webs: the ultimate missing links - Kevin D. Lafferty; Stefano Allesina; Matias Arim; Cherie J. Briggs; Giulio De Leo; Andrew P. Dobson; Jennifer A. Dunne; Pieter T. J. Johnson; Armand M. Kuris; David J. Marcogliese; Neo D. Martinez; Jane Memmott; et al. (Ecology Letters, 2008)
Parasitism is the most common consumer strategy among organisms, yet only recently has there been a call for the inclusion of infectious disease agents in food webs. The value of this effort hinges on whether parasites affect food‐web properties. Increasing evidence suggests that parasites have the potential to uniquely alter food‐web topology in terms of chain length, connectance and robustness. In addition, parasites might affect food‐web stability, interaction strength and energy flow. Food‐web structure also affects infectious disease dynamics because parasites depend on the ecological networks in which they live. Empirically, incorporating parasites into food webs is straightforward. We may start with existing food webs and add parasites as nodes, or we may try to build food webs around systems for which we already have a good understanding of infectious processes. In the future, perhaps researchers will add parasites while they construct food webs. Less clear is how food‐web theory can accommodate parasites. This is a deep and central problem in theoretical biology and applied mathematics. For instance, is representing parasites with complex life cycles as a single node equivalent to representing other species with ontogenetic niche shifts as a single node? Can parasitism fit into fundamental frameworks such as the niche model? Can we integrate infectious disease models into the emerging field of dynamic food‐web modelling? Future progress will benefit from interdisciplinary collaborations between ecologists and infectious disease biologists.

Stable isotope profiles of partially migratory salmonid populations in Atlantic rivers of Patagonia - J. E. Ciancio; M. A. Pascual; F. Botto; M. Amaya‐Santi; S. O’Neal; C. Riva Rossi; O. Iribarne (Journal of Fish Biology, 2008)
In the present study, profiles of stable isotope composition were characterized for two species with partially migratory populations in rivers along the latitudinal gradient of Patagonia, brown trout Salmo trutta and rainbow trout Oncorhynchus mykiss . The effects of factors ( e.g. ontogeny of fishes, location, species and fasting) that may influence the stable isotope analysis (SIA) were evaluated, as was SIA evaluated as a tool to assign individual fish to their corresponding ecotype. Anadromous fishes exhibited enriched δ 15 N (15·2 ± 1·0‰; mean ± s . d .) and δ 13 C (−19·2 ± 1·3‰) relative to resident fishes’δ 15 N (8·8 ± 1·1‰) and δ 13 C (−23·2 ± 2·5‰). For both species, the difference in δ 15 N was larger between resident (range 6·8–10·7‰) and anadromous (range 14·3–17·8‰) fishes than that in δ 13 C. Values of δ 13 C, while not as dramatically contrasting in rainbow trout, provided a powerful anadromy marker for brown trout in the region. Increases were found in both δ 15 N and δ 13 C during the spawning migration of anadromous rainbow trout, most likely due to fasting. Differences in stable isotopes between location, size and species were found, suggesting different stable isotopes base levels in freshwater environments and different trophic levels and feeding location of anadromous populations. The SIA was demonstrated as a powerful tool for ecotype discrimination in Patagonian Rivers, overriding any effect of sampling location, size or species.

Purification and Partial Characterization of Novel Bacteriocin L23 Produced by Lactobacillus fermentum L23 - Liliana M. Pascual; María B. Daniele; Walter Giordano; María C. Pájaro; Isabel L. Barberis (Current Microbiology, 2008)

Territory characteristics and coexistence with heterospecifics in the Dartford warbler Sylvia undata across a habitat gradient - Pere Pons; Josep M. Bas; Roger Prodon; Núria Roura-Pascual; Miguel Clavero (Behavioral Ecology and Sociobiology, 2008)

Inoculation of Pinus halepensis Mill. with selected ectomycorrhizal fungi improves seedling establishment 2 years after planting in a degraded gypsum soil - Ana Rincón; M. R. de Felipe; M. Fernández-Pascual (Mycorrhiza, 2007)

The senescence-accelerated mouse (SAM-P8) as a model for the study of vascular functional alterations during aging - Silvia Lloréns; Raquel M Melero-Fernandez de Mera; Alejandro Pascual; Ana Prieto-Martín; Yolanda Mendizábal; Carlos de Cabo; Eduardo Nava; Joaquín Jordán (Biogerontology, 2007)

Localization and thiol dependancy of endogenous nitro compounds-mediating urethral photo-relaxation - D. Triguero; M. González-Herreros; G. Costa; A. García-Pascual (Pflügers Archiv - European Journal of Physiology, 2007)

Energy balance of Octopus maya fed crab or an artificial diet - Carlos Rosas; Gerard Cuzon; Cristina Pascual; Gabriela Gaxiola; Darwin Chay; Nelda López; Teresita Maldonado; Pedro M. Domingues (Marine Biology, 2007)

Introduction history of Drosophila subobscura in the New World: a microsatellite‐based survey using ABC methods - M. PASCUAL; M. P. CHAPUIS; F. MESTRES; J. BALANYÀ; R. B. HUEY; G. W. GILCHRIST; L. SERRA; A. ESTOUP (Molecular Ecology, 2007)
Drosophila subobscura is a Palearctic species that was first observed in South and North America in the early 1980s, and that rapidly invaded broad latitudinal ranges on both continents. To trace the source and history of this invasion, we obtained genotypic data on nine microsatellite loci from two South American, two North American and five European populations of D. subobscura. We analysed these data with traditional statistics as well as with an approximate Bayesian computation (ABC) framework. ABC methods yielded the strongest support for the scenario involving a serial introduction with founder events from Europe into South America, and then from South America into North America. Stable effective population size of the source population was very large (around one million individuals), and the propagule size was notably smaller for the introduction into South America (i.e. high bottleneck severity index with only a few effective founders) but considerably larger for the subsequent introduction into North America (i.e. low bottleneck severity index with around 100–150 effective founders). Finally, the Mediterranean region of Europe (and most likely Barcelona from the localities so far analysed) is proposed as the source of the New World flies, based on mean individual assignment statistics.

The genetic structure of the loggerhead sea turtle (Caretta caretta) in the Mediterranean as revealed by nuclear and mitochondrial DNA and its conservation implications - C. Carreras; M. Pascual; L. Cardona; A. Aguilar; D. Margaritoulis; A. Rees; O. Turkozan; Y. Levy; A. Gasith; M. Aureggi; M. Khalil (Conservation Genetics, 2007)

Intra‐population variation in anadromy and reproductive life span in rainbow trout introduced in the Santa Cruz River, Argentina - C. Riva‐Rossi; M. A. Pascual; J. A. Babaluk; M. García‐Asorey; N. M. Halden (Journal of Fish Biology, 2007)
Scale patterns, maturational status and otolith microchemistry (strontium to calcium ratios) were analysed in sympatric anadromous and non‐anadromous rainbow trout Oncorhynchus mykiss in the Santa Cruz River (Patagonia, Argentina) to investigate the life‐history differences of anadromous and non‐anadromous lifestyles and the association between maternal origin and progeny life history. The analyses revealed that both forms can give rise to one another, indicating a single population with alternative phenotypes. Anadromous fish smolted at ages 2 and 3 years, matured after 1 to 2 years in the ocean, and survived up to 11 years, spawning up to eight times. Non‐anadromous fish survived up to 6 years, spawning up to three times. The extended reproductive life span associated with anadromy in this river suggests that increased energetic and physiological demands associated with ocean migration may not necessarily result in reduced postspawning survival, as has been suggested for salmonids in general. Alternatively, reduction in parity may be regarded as the evolutionary outcome of reproductive traits resulting from the adoption of anadromy ( i.e. augmented reproductive investment) coupled with long‐range migrations to and from the ocean. The life‐history patterns of Santa Cruz River rainbow trout provide a natural experiment for investigating the evolutionary transition and maintenance of anadromy and non‐anadromy within salmonid populations.

Association of the F352V variant of the Klotho gene with bone mineral density - José A. Riancho; Carmen Valero; José L. Hernández; Fernando Ortiz; Ana Zarrabeitia; María A. Alonso; Nicolás Peña; M. Asunción Pascual; Jesús González-Macías; María T. Zarrabeitia (Biogerontology, 2007)

Xenostrobus securis (Lamarck, 1819) (Mollusca: Bivalvia): first report of an introduced species in Galician waters - M. E. Garci; J. E. Trigo; S. Pascual; A. F. González; F. Rocha; A. Guerra (Aquaculture International, 2007)

Wavelet-vaguelette decomposition of spatiotemporal random fields - M. D. Ruiz-Medina; J. M. Angulo; R. Fernández-Pascual (Stochastic Environmental Research and Risk Assessment, 2007)

Serotonin transporter occupancy induced by paroxetine in patients with major depression disorder: a 123I-ADAM SPECT study - Ana M. Catafau; Victor Perez; Pedro Plaza; Juan-Carlos Pascual; Santiago Bullich; Marina Suarez; Maria M. Penengo; Iluminada Corripio; Dolors Puigdemont; Monica Danus; Javier Perich; Enric Alvarez (Psychopharmacology, 2006)

Molecular characterization and evaluation of mycorrhizal capacity of Suillus isolates from Central Spain for the selection of fungal inoculants - Beatriz Ruiz-Díez; Ana M. Rincón; María R. de Felipe; Mercedes Fernández-Pascual (Mycorrhiza, 2006)

Population structure within and between subspecies of the Mediterranean triplefin fish Tripterygion delaisi revealed by highly polymorphic microsatellite loci - J. CARRERAS‐CARBONELL; E. MACPHERSON; M. PASCUAL (Molecular Ecology, 2006)
Although F ST values are widely used to elucidate population relationships, in some cases, when employing highly polymorphic loci, they should be regarded with caution, particularly when subspecies are under consideration. Tripterygion delaisi presents two subspecies that were investigated here, using 10 microsatellite loci. A Bayesian approach allowed us to clearly identify both subspecies as two different evolutionary significant units. However, low F ST values were found between subspecies as a consequence of the large number of alleles per locus, while homoplasy could be disregarded as indicated by the standardized genetic distance . Heterozygosity saturation was observed in highly polymorphic loci containing more than 15 alleles, and this threshold was used to define two loci pools. The less variable loci pool revealed higher genetic variance between subspecies, while the more variable pool showed higher genetic variance between populations. Furthermore, higher differentiation was also observed between populations using with the more variable loci. Nonetheless, a more reliable population structure within subspecies was obtained when all loci were included in the analyses. In T. d. xanthosoma , isolation by distance was detected between the eight analysed populations, and six genetically homogeneous clusters were inferred by Bayesian analyses that are in accordance with F ST values. The neighbourhood‐size method also indicated rather small dispersal capabilities. In conclusion, in fish with limited adult and larval dispersal capabilities, continuous rocky habitat seems to allow contact between populations and prevent genetic differentiation, while large discontinuities of sand or deep‐water channels seems to reduce gene flow.

Spatial Associations, Size–Distance Relationships and Population Structure of Two Dominant Life Forms in a Semiarid Enclave of the Venezuelan Andes - Daniel M. Larrea-Alcázar; Pascual J. Soriano (Plant Ecology, 2006)

Incidence and risk factors associated with urinary tract infection in diabetic patients with and without asymptomatic bacteriuria - M. C. Ribera; R. Pascual; D. Orozco; C. Barba; V. Pedrera; V. Gil (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Micro-array analyses decipher exceptional complex familial chromosomal rearrangement - Christine Fauth; Susan M. Gribble; Keith M. Porter; Montserrat Codina-Pascual; Bee Ling Ng; Jürgen Kraus; Sabine Uhrig; Jürgen Leifheit; Thomas Haaf; Heike Fiegler; Nigel P. Carter; Michael R. Speicher (Human Genetics, 2006)

Natural Colonization and Establishment of a Chinook Salmon, Oncorhynchus tshawytscha, Population in the Santa Cruz River, an Atlantic Basin of Patagonia - Javier E. Ciancio; Miguel A. Pascual; Julio Lancelotti; Carla M. Riva Rossi; Florencia Botto (Environmental Biology of Fishes, 2005)

Engrailed-ZmOCL1 fusions cause a transient reduction of kernel size in maize - Abdel-Sabour Khaled; Vanessa Vernoud; Gwyneth C. Ingram; Pascual Perez; Xavier Sarda; Peter M. Rogowsky (Plant Molecular Biology, 2005)

Aggregata andresi n. sp. (Apicomplexa: Aggregatidae) from the ommastrephid squid Martialia hyadesi in the SW Atlantic Ocean and some general remarks on Aggregata spp. in cephalopod hosts - C. Gestal; Ch. M. Nigmatullin; F. G. Hochberg; A. Guerra; S. Pascual (Systematic Parasitology, 2005)

Heavy Metals and Hydrocarbons in Sediments from Three Lakes from San Miguel, Chiapas, Mexico - A. Pascual-Barrera; G. Gold-Bouchot; V. Ceja-Moreno; M. del Ro-Garca (Bulletin of Environmental Contamination and Toxicology, 2004)

Plant availability of heavy metals in a soil amended with a high dose of sewage sludge under drought conditions - Inmaculada Pascual; M. Carmen Antoln; Carlos Garca; Alfredo Polo; Manuel Snchez-Daz (Biology and Fertility of Soils, 2004)

Phylogeography and speciation of colour morphs in the colonial ascidian Pseudodistoma crucigaster - I. TARJUELO; D. POSADA; K. A. CRANDALL; M. PASCUAL; X. TURON (Molecular Ecology, 2004)
Variation in pigmentation is common in marine invertebrates, although few studies have shown the existence of genetic differentiation of chromatic forms in these organisms. We studied the genetic structure of a colonial ascidian with populations of different colour morphs in the northwestern Mediterranean. A fragment of the c oxidase subunit 1 (COI) mitochondrial gene was sequenced in seven populations of Pseudodistoma crucigaster belonging to three different colour morphs (orange, yellow and grey). Maximum likelihood analyses showed two well‐supported clades separating the orange morph from the yellow‐grey morphotypes. Genetic divergence between these clades was 2.12%, and γ ST values between populations of the two clades were high (average 0.936), pointing to genetic isolation. Nested clade and coalescence analyses suggest that a past fragmentation event may explain the phylogeographical origin of these two clades. Non‐neutral mtDNA evolution is observed in our data when comparing the two clades, showing a significant excess of nonsynonymous polymorphism within the yellow–grey morphotype using the McDonald–Kreitman test, which is interpreted as further support of reproductive isolation. We conclude that the two clades might represent separate species. We compare the population genetic differentiation found with that estimated for other colonial and solitary ascidian species, and relate it to larval dispersal capabilities and other life‐history traits.

Alfalfa (Medicago sativa) Somatic Embryogenesis: Genetic Control and Introduction of Favourable Alleles into Elite Argentinean Germplasm - Roxana Moltrasio; Claudio G. Robredo; María Cristina Gómez; Antonio H. Díaz Paleo; Daniel G. Díaz; Raúl D. Rios; Pascual M. Franzone (Plant Cell, Tissue and Organ Culture (PCTOC), 2004)

Strong population structure in the marine sponge Crambe crambe (Poecilosclerida) as revealed by microsatellite markers - S. Duran; M. Pascual; A. Estoup; X. Turon (Molecular Ecology, 2004)
Different categories of molecular markers have been used so far to study the population structure of sponges. However, these markers often did not have the resolution power to address precisely questions on structuring processes, especially at the intrapopulational level. In this study we show that microsatellites fulfil these expectations, allowing a fine description of population structure at different geographical scales in the marine sponge Crambe crambe . Specimens were collected in 11 locations, representing most of the Atlanto‐Mediterranean range of the species, and were analysed at six loci. As expected for a sessile invertebrate with lecitotrophic larvae, high levels of between‐population structure were found ( F ST = 0.18) and a significant isolation‐by‐distance pattern was observed. A strong genetic structure was also found within sampled sites ( F IS = 0.21) that may be explained by several factors including inbreeding, selfing and the Wahlund effect. In spite of a sampling design planned to avoid the sampling of clones, genotypically identical individuals for the six loci were found in some locations. The significance of these potential clones is discussed and their effect on the observed pattern of population structure assessed. Patterns of allelic distribution within populations suggest the possibility of a recent colonization of the Atlantic range from the Mediterranean Sea.

Low levels of genetic variation in mtDNA sequences over the western Mediterranean and Atlantic range of the sponge Crambe crambe (Poecilosclerida) - S. Duran; M. Pascual; X. Turon (Marine Biology, 2004)

ZmEBE genes show a novel, continuous expression pattern in the central cell before fertilization and in specific domains of the resulting endosperm after fertilization - Jean-Louis Magnard; Gaëlle Lehouque; Agnès Massonneau; Nathalie Frangne; Thierry Heckel; José F. Gutierrez-Marcos; Pascual Perez; Christian Dumas; Peter M. Rogowsky (Plant Molecular Biology, 2003)

Bioaerosol emission from wastewater treatment plants - Leonor Pascual; Sara Pérez-Luz; M. Adela Yáñez; Ana Santamaría; Karina Gibert; Miquel Salgot; David Apraiz; Vicente Catalán (Aerobiologia, 2003)

A negative regulator of light-inducible carotenogenesis in Mucor circinelloides - E. Navarro; J. Lorca-Pascual; M. Quiles-Rosillo; F. Nicolás; V. Garre; S. Torres-Martínez; R. Ruiz-Vázquez (Molecular Genetics and Genomics, 2001)

Surface EMG shows distinct populations of muscle activity when measured during sustained sub-maximal exercise - James M. Wakeling; Silvia A. Pascual; Benno M. Nigg; Vinzenz Tscharner (European Journal of Applied Physiology, 2001)

Cryptic species of Clavelina (Ascidiacea) in two different habitats: harbours and rocky littoral zones in the northwestern Mediterranean - Tarjuelo I.; Posada D.; Crandall K.; Pascual M.; Turon X. (Marine Biology, 2001)

Influence of type II 5′ deiodinase on TSH content in diabetic rats - C. Aláez; R. Calvo; M. J. Obregón; C. Alvarez; L. Goya; F. Escrivá; M. A. Martín; A. M. Pascual-Leone (Journal of Physiology and Biochemistry, 2001)

Hepatic coccidiosis of the blue whiting, Micromesistius poutassou (Risso), and horse mackerel, Trachurus trachurus (L.), from Galician waters - E Abollo; M Calvo; S Pascual (Journal of Fish Diseases, 2001)
The aetiology, epidemiology and pathology of coccidiosis in commercially‐exploited populations of Micromesistius poutassou and Trachurus trachurus from Galician waters were investigated. Sporogonic stages of Goussia clupearum and G. cruciata were found in the liver. Although the descriptive statistics of Goussia infrapopulations and demographic infection values were always higher in M. poutassou than in T. trachurus , parasite distribution was highly skewed for both coccidian species. In both fish species, the number of oöcysts showed a similar cumulative effect as parasite counts increased with increasing length and weight of fish, but did not change with host sex or sexual maturity. Pathological changes in infected liver parenchyma of both species were moderate (in T. trachurus ) to severe (in M. poutassou ), with greatly reduced livers in the most heavily infected fish. Large areas of liver tissue were replaced with oöcysts. Host response to infection included the formation of a fibrous capsule prior to infiltration by melanin and lymphocytes. Although post‐recruit individuals of both fish species apparently tolerate a severe infection, there was statistical evidence of a serious contribution by the parasite to poor body condition in M. poutassou shown by changes in the hepatosomatic and K‐Fulton indices and in the length‐ to‐weight relationship.

The Introduced Green Alga Caulerpa Taxifolia Continues to Spread in the Mediterranean - Alexandre Meinesz; Thomas Belsher; Thierry Thibaut; Boris Antolic; Karim Ben Mustapha; Charles-Francçois Boudouresque; Danièle Chiaverini; Francesco Cinelli; Jean-Michel Cottalorda; Aslam Djellouli; Amor El Abed; Carla Orestano; et al. (Biological Invasions, 2001)

Immunolocalization of alkaloids and X-ray microanalysis of elements in lupin seeds - J. M. Pozuelo; M. M. Lucas; C. de Lorenzo; M. Fernández-Pascual; S. Maldonado; M. R. de Felipe (Protoplasma, 2001)

Interindividual variability of the modulatory effects of repetitive transcranial magnetic stimulation on cortical excitability - Fumiko Maeda; Julian P. Keenan; Jose M. Tormos; Helge Topka; Alvaro Pascual-Leone (Experimental Brain Research, 2000)

Altered regulation of calcium channels and exocytosis in single human pheochromocytoma cells - Jesús M. Hernández-Guijo; Luis Gandía; Inmaculada Cuchillo-Ibáñez; Almudena Albillos; Jesús Novalbos; Fernando Gilsanz; Eduardo Larrañaga; Ricardo de Pascual; Francisco Abad; Antonio G. García (Pflügers Archiv - European Journal of Physiology, 2000)

Long-term suppression of Pythium ultimum in arid soil using fresh and composted municipal wastes - J. A. Pascual; T. Hernandez; C. Garcia; F.A.A.M. De Leij; J. M. Lynch (Biology and Fertility of Soils, 2000)

The Iberian type of volcano-sedimentary massive sulphide deposits - R. Sáez; E. Pascual; M. Toscano; G. R. Almodóvar (Mineralium Deposita, 1999)

Effects of Food Restriction on Food Avoidance and Risk of Acute Poisoning of Captive Feral Pigeons from Fonofos-Treated Seeds - J. A. Pascual; S. L. Fryday; A. D. M. Hart (Archives of Environmental Contamination and Toxicology, 1999)

Relative and combined effects of ethanol and protein deficiency on strontium and barium bone content and fecal and urinary excretion - E. Gonzalez-Reimers; F. Rodriguez-Moreno; A. Martinez-Riera; A. Mas-Pascual; E. Delgado-Ureta; L. Galindo-Martin; M. Arnay-de La Rosa; F. Santolaria-Fernandez (Biological Trace Element Research, 1999)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Human adrenal chromaffin cell calcium channels: drastic current facilitation in cell clusters, but not in isolated cells - Luis Gandía; Inés Mayorgas; Pedro Michelena; Inmaculada Cuchillo; Ricardo de Pascual; Francisco Abad; Jesús M. Novalbos; Eduardo Larrañaga; A. G. García (Pflügers Archiv - European Journal of Physiology, 1998)

Separation of calcium channel current components in mouse chromaffin cells superfused with low- and high-barium solutions - Jesús M. Hernández-Guijo; Ricardo de Pascual; Antonio G. García; L. Gandía (Pflügers Archiv - European Journal of Physiology, 1998)

Effect of focal cerebellar lesions on procedural learning in the serial reaction time task - M. Gmez-Beldarrain; J. C. Garca-Monc; B. Rubio; A. Pascual-Leone (Experimental Brain Research, 1998)

Subcellular localization of glycoprotein epitopes during the development of lupin root nodules - C. A. de Lorenzo; M. M. Fernández-Pascual; M. R. de Felipe (Protoplasma, 1998)

Geology and genesis of the Aznalcóllar massive sulphide deposits, Iberian Pyrite Belt, Spain - G. R. Almodóvar; R. Sáez; J. M. Pons; A. Maestre; M. Toscano; E. Pascual (Mineralium Deposita, 1997)

The volcanic-hosted massive sulphide deposits of the Iberian Pyrite Belt - J. M. Leistel; E. Marcoux; D. Thiéblemont; C. Quesada; A. Sánchez; G. R. Almodóvar; E. Pascual; R. Sáez (Mineralium Deposita, 1997)

Energy content of rotifers (Brachionus plicatilis and Brachionus rotundiformis) in relation to temperature - M. Yúfera; G. Parra; E. Pascual (Hydrobiologia, 1997)

Identification of de novo deletions at the NF1 gene: no preferential paternal origin and phenotypic analysis of patients - M. Carmen Valero; Ignacio Pascual-Castroviejo; E. Velasco; Felipe Moreno; Concepción Hernández-Chico (Human Genetics, 1997)

Changes in the microbial activity of an arid soil amended with urban organic wastes - J. A. Pascual; C. García; T. Hernandez; M. Ayuso (Biology and Fertility of Soils, 1997)

Diagnosis of sibling species of Drosophila involved in the colonization of North America by D. subobscura - M. Pascual; J. Balanyà; A. Latorre; L. Serra (Molecular Ecology, 1997)
To determine the effects of the recent colonization of the west coast of North America by the Palaearctic species Drosophila subobscura on the dynamics of the Drosophila populations, the sibling species D. athabasca and D. azteca must be classified unambiguously. We have characterized these two species using three molecular techniques: allozymes, mtDNA and RAPDs. All three techniques allow the classification of any individual as belonging to either species. The study of five localities in northern California and southern Oregon show that the area of overlap is larger than previously described.

Coplanar Polychlorinated Biphenyl Congeners in Shark Livers from the North-Western African Atlantic Ocean - R. Serrano; M. A. Fernández; L. M. Hernández; M. Hernández; P. Pascual; R. M. Rabanal; M. J. González (Bulletin of Environmental Contamination and Toxicology, 1997)

Serum aluminum levels in alzheimer’s disease and other senile dementias - M. D. Zapatero; A. Garcia de Jalon; F. Pascual; M. L. Calvo; J. Escanero; A. Marro (Biological Trace Element Research, 1995)